Optical film, polarizing plate, image display device, and method for selecting optical film

The optical film with a low refractive index layer on a plastic film addresses rainbow pattern unevenness and color tone changes by controlling interference and reflectivity, ensuring effective rainbow spot elimination and uniform color tone across viewing angles.

CN119200071APending Publication Date: 2024-12-27DAI NIPPON PRINTING CO LTD

Patent Information

Application Number
CN202411507433.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-10-21
Filing Date
2021-10-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing optical films used in image display devices suffer from rainbow pattern unevenness and color tone changes when observed from oblique directions, which are not adequately addressed by existing technologies.

Method used

An optical film with a low refractive index layer on a plastic film, where the film has a slow and fast axis, and specific conditions are met to control the sum of the square differences in a* and b* values of the L*a*b* colorimetric system, along with controlled reflectivity and refractive index ratios, to minimize interference and enhance color tone uniformity.

Benefits of technology

The optical film effectively eliminates rainbow spots and improves color tone uniformity when observed with the naked eye and from oblique directions, maintaining high mechanical strength and reflectivity within specified ranges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119200071A_ABST
    Figure CN119200071A_ABST
Patent Text Reader

Abstract

The invention provides an optical film, a polarizing plate, an image display device, and a method for selecting the optical film. An optical film having a low refractive index layer on a plastic film, the plastic film having a slow axis and a fast axis, the slow axis being an axis having a maximum in-plane refractive index, the fast axis being an axis orthogonal to the slow axis in a plane of the plastic film, and the low refractive index layer being located on a surface of the optical film. Radial polarized light enters from a surface of the optical film on the opposite side from the low refractive index layer under predetermined conditions, and a * value and b * value of the L * a * b * color system of transmitted light of the linearly polarized light are measured at 11 measurement points having different angles. On the basis of measurement at 11 measurement points, the sum of the second power of the a * difference between adjacent measurement points and the second power of the b * difference between adjacent measurement points is calculated at 10 adjacent points. In the optical film, sigma T, which represents the sum of the sums, is within a prescribed range.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese invention patent application with an application date of October 21, 2021, an invention name of "Optical film, polarizing plate, image display device and method for selecting optical film", and an application number of 202180071031.4 (PCT / JP2021 / 038887). Technical Field

[0002] The present disclosure relates to an optical film, a polarizing plate, an image display device, and a method for selecting an optical film. Background Art

[0003] Various optical plastic films are often used in optical components such as image display devices. For example, in an image display device having a polarizing plate on a display element, a plastic film is used to protect the polarizer constituting the polarizing plate. In this specification, a "plastic film for protecting a polarizer" is sometimes referred to as a "polarizer protective film".

[0004] The plastic film for image display devices used as a polarizer protective film or the like is preferably a plastic film having excellent mechanical strength. Therefore, as the plastic film for image display devices, a stretched plastic film is preferably used.

[0005] When a stretched plastic film is placed on a polarizer, the stretched plastic film disturbs the polarization state of the linearly polarized light passing through the polarizer, so there is a problem that rainbow pattern unevenness is observed. In order to solve the problem of rainbow spots, the techniques of patent documents 1 to 3 are proposed. Hereinafter, in this specification, "rainbow pattern unevenness" is sometimes referred to as "rainbow unevenness".

[0006] Patent document 1 discloses a liquid crystal display device that can eliminate rainbow spots when observing images through polarized sunglasses by setting the light source of the image display device to a specific white light source, increasing the in-plane phase difference (retardation) of the stretched plastic film to above 3000nm and below 30000nm, and configuring the absorption axis of the polarizer and the slow axis of the stretched plastic film to be approximately 45 degrees.

[0007] However, the proposal of Patent Document 1 requires the use of a stretched plastic film having a large in-plane phase difference. Furthermore, a stretched plastic film having a large in-plane phase difference is generally uniaxially stretched, and therefore has problems such as being easily cracked in the stretching direction.

[0008] Patent Document 2 discloses a polarizing plate protective film having a reflectance within a specific range at a Brewster angle. Patent Document 3 discloses a polarizing plate protective film having a difference of 20% or less between the reflectance of a P wave and the reflectance of an S wave at an incident angle of 50 degrees.

[0009] The polarizing plate protective films of Patent Documents 2 and 3 reduce the reflectivity difference between the polarization components of light from the inside of the image display device toward the observer side, i.e., the P wave and the S wave, thereby eliminating rainbow spots when observed with the naked eye without increasing the in-plane phase difference of the film as in Patent Document 1.

[0010] The polarizing plate protective films of Patent Documents 2 and 3 can improve the rainbow spots when observed with the naked eye to a certain extent. However, the polarizing plate protective films of Patent Documents 2 and 3 have the problem that the color tone changes depending on the angle of observation. That is, the polarizing plate protective films of Patent Documents 2 and 3 cannot satisfy the uniformity of the color tone when observed from an oblique direction.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Application Publication No. 2011-107198

[0014] Patent Document 2: Japanese Patent Application Publication No. 2009-14886

[0015] Patent Document 3: Japanese Patent Application Publication No. 2010-204630 Summary of the invention

[0016] Problems to be solved by the invention

[0017] The object of the present disclosure is to provide an optical film that can eliminate rainbow spots when observed with the naked eye and has good uniformity of color tone when observed from an oblique direction, as well as a polarizing plate and an image display device using the optical film. The object of the present disclosure is to provide a method for selecting an optical film that can eliminate rainbow spots when observed with the naked eye and has good uniformity of color tone when observed from an oblique direction.

[0018] Means for solving problems

[0019] The present disclosure provides the following [1] to

[12] .

[0020] [1] An optical film having a low refractive index layer on a plastic film, wherein:

[0021] The plastic film has: a slow axis, which is an axis with the largest refractive index in a plane; and a fast axis, which is an axis orthogonal to the slow axis in the plane of the plastic film.

[0022] The low refractive index layer is located on the surface of the optical film.

[0023] The optical film has a Σ calculated under the following measurement condition 1. T In the area exceeding 0.04 and less than 0.20,

[0024] <Measurement Condition 1>

[0025] A linearly polarized light is incident from the surface of the optical film opposite to the low refractive index layer, the linearly polarized light as the incident light is defined as light L1, and the transmitted light after the light L1 passes through the optical film is defined as light L2;

[0026] The light L1 is made incident on the optical film at the following angle, wherein the angle is such that the elevation angle of the vibration direction of the light L1 is greater than 50 degrees and less than 70 degrees based on the plane of the optical film, while the angle formed by the slow axis and the vibration direction of the light L1 is fixed at 45 degrees, and the elevation angle is changed by 2 degrees within the range of greater than 50 degrees and less than 70 degrees, and the light L2 is measured at 11 elevation angles, and the light L2 is measured at 11 measurement points through the above-mentioned measurement;

[0027] The light L2 is converted into the conditions of C light source and a viewing angle of 2 degrees, and the a* value and b* value of the L*a*b* colorimetric system are defined as a*n and b*n for the light L2 at the nth measurement point among the 11 measurement points, and the a* value and b* value of the L*a*b* colorimetric system are defined as a*n1 and b*n1 for the light L2 at the n+1th measurement point among the 11 measurement points;

[0028] Based on the measurements of the 11 measurement points, the sum of the square of the difference between the a* of the adjacent measurement points and the square of the difference between the b* of the adjacent measurement points is calculated, the sum is calculated at each of the 10 adjacent points, and ∑ T , the Σ T It can be expressed by the following formula 1:

[0029] ∑ T =∑[{a*na*n1} 2 +{b*nb*n1} 2 ] (Formula 1).

[0030] [2] The optical film according to [1], wherein

[0031] Based on the measurement of the 11 measurement points, when the maximum value of a* is defined as a*max, the minimum value of a* is defined as a*min, the maximum value of b* is defined as b*max, and the minimum value of b* is defined as b*min, the following equations 2-1 and 2-2 are satisfied:

[0032] a*max-a*min≤0.250 (Formula 2-1)

[0033] b*max-b*min≤0.350 (Formula 2-2).

[0034] [3] The optical film according to [1] or [2], wherein

[0035] Based on the measurements of the 11 measurement points, the sum of the square of the difference between the a* of the adjacent measurement points and the square of the difference between the b* of the adjacent measurement points is calculated. When the sum is defined as S, S can be expressed by the following formula 3. S is calculated at 10 adjacent points respectively, and the maximum value of S of the 10 points is defined as S MAX When S MAX is 0.010 or more and 0.050 or less,

[0036] S={a*na*n1} 2 +{b*nb*n1} 2 (Formula 3).

[0037] [4] The optical film according to any one of [1] to [3], wherein

[0038] When the visual reflectance Y value of the optical film is defined as R (%), the R and the Σ T The product is greater than or equal to 0.05 and less than or equal to 0.25.

[0039] [5] The optical film according to any one of [1] to [4], wherein

[0040] When the average refractive index of the low refractive index layer is defined as n1 and the average refractive index of the layer adjacent to the low refractive index layer is defined as n2, n2 / n1 is less than 1.23.

[0041] [6] The optical film according to any one of [1] to [4], wherein

[0042] When the average refractive index of the low refractive index layer is defined as n1 and the average refractive index of the layer adjacent to the low refractive index layer is defined as n2, n2 / n1 is 1.05 or more and less than 1.23.

[0043] [7] The optical film according to any one of [1] to [6], wherein

[0044] The plastic film has an in-plane phase difference of 2500 nm or less.

[0045] [8] The optical film according to any one of [1] to [7], wherein

[0046] The plastic film satisfies the following condition A:

[0047] <Condition A>

[0048] A sample of 50 mm in length and 50 mm in width is cut out from the plastic film, and five locations in total, including one in the center of the sample and four locations each 10 mm from the four corners of the sample toward the center, are used as measurement locations;

[0049] The directions of the slow axis are measured at the five locations of the sample, and the angles formed by any one side of the sample and the direction of the slow axis of each measured location are defined as D1, D2, D3, D4, and D5, respectively. The difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is greater than 1.5 degrees.

[0050] [9] The optical film according to any one of [1] to [8], wherein

[0051] One or more layers selected from a hard coat layer and an anti-glare layer are provided between the plastic film and the low refractive index layer.

[0052]

[10] A polarizing plate comprising: a polarizer; a first transparent protective plate located on one side of the polarizer; and a second transparent protective plate located on the other side of the polarizer, wherein:

[0053] At least one of the first transparent protective plate and the second transparent protective plate is the optical film according to any one of [1] to [9], and a surface of the optical film on the low refractive index layer side faces the opposite side to the polarizer.

[0054]

[11] An image display device comprising: a display element; and a polarizer and an optical film disposed on the light emitting surface side of the display element, wherein:

[0055] The optical film is the optical film described in any one of [1] to [7], and the surface of the optical film on the low refractive index layer side faces the opposite side to the display element.

[0056]

[12] A method for selecting an optical film for an image display device, wherein the image display device has a polarizer and an optical film on a light emitting surface of a display element, wherein:

[0057] An optical film X satisfying the following determination conditions (1) to (4) is selected as the optical film.

[0058] (1) is an optical film X having a low refractive index layer on a plastic film;

[0059] (2) The plastic film has: a slow axis, which is an axis with the largest refractive index in a plane; and a fast axis, which is an axis orthogonal to the slow axis in the plane of the plastic film;

[0060] (3) The low refractive index layer is located on the surface of the optical film X; and

[0061] (4) The optical film X has a Σ that satisfies the Σ calculated under the above measurement condition 1. T The area that is greater than 0.04 and less than 0.20.

[0062] Effects of the Invention

[0063] The optical film disclosed herein, and the polarizing plate and image display device using the optical film can eliminate rainbow spots when observed with the naked eye, and can improve the uniformity of color tone when observed from an oblique direction. The method for selecting an optical film disclosed herein can efficiently select an optical film that can eliminate rainbow spots when observed with the naked eye, and can improve the uniformity of color tone when observed from an oblique direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 is a cross-sectional view showing one embodiment of the optical film of the present disclosure.

[0065] Figure 2 This is a schematic diagram showing an example of measurement performed under measurement condition 1.

[0066] Figure 3 is a cross-sectional view showing one embodiment of the polarizing plate of the present disclosure.

[0067] Figure 4 is a cross-sectional view showing one embodiment of the image display device of the present disclosure.

[0068] Figure 5 This is a plan view of five measurement positions in a sample for explaining how to calculate the in-plane phase difference and the like from the sample.

[0069] Figure 6 It is a figure which shows schematically the state of a continuous folding test.

[0070] Figure 7 This is a schematic cross-sectional view of a device for measuring the erosion rate.

[0071] Figure 8 This is a schematic diagram showing a state in which a plastic film is worn away by a test liquid containing pure water and spherical silica ejected from an ejection unit. DETAILED DESCRIPTION

[0072] Hereinafter, embodiments of the optical film of the present disclosure will be described.

[0073] The optical film disclosed in the present invention has a low refractive index layer on a plastic film, the plastic film having: an axis with the largest refractive index in a plane, i.e., a slow axis; and an axis in the plane of the plastic film orthogonal to the slow axis, i.e., a fast axis, the low refractive index layer being located on the surface of the optical film, and the optical film having a Σ T The area that is greater than 0.04 and less than 0.20.

[0074] <Measurement Condition 1>

[0075] Linearly polarized light is incident from the surface of the optical film opposite to the low refractive index layer. The incident linearly polarized light is defined as light L1. Transmitted light after the light L1 passes through the optical film is defined as light L2.

[0076] The light L1 is made incident on the optical film at the following angle, wherein the angle is an angle in which the elevation angle of the vibration direction of the light L1 is greater than 50 degrees and less than 70 degrees based on the plane of the optical film, on the basis of fixing the angle formed by the slow axis and the vibration direction of the light L1 at 45 degrees. The light L2 is measured at 11 elevation angles by varying the elevation angle by 2 degrees within the range of greater than 50 degrees and less than 70 degrees. Through the above measurement, the light L2 is measured at 11 measurement points.

[0077] The light L2 is converted to the conditions of C light source and viewing angle of 2 degrees. For the light L2 at the nth measurement point among the 11 measurement points, the a* value and b* value of the L*a*b* colorimetric system are defined as a*n and b*n. In addition, for the light L2 at the n+1th measurement point among the 11 measurement points, the a* value and b* value of the L*a*b* colorimetric system are defined as a*n1 and b*n1.

[0078] Based on the measurements of the 11 measurement points, the sum of the square of the difference between the a* of the adjacent measurement points and the square of the difference between the b* of the adjacent measurement points is calculated. The sum is calculated at each of the 10 adjacent points, and ∑ T The Σ T It can be represented by the following formula 1.

[0079] ∑ T =∑[{a*na*n1} 2 +{b*nb*n1} 2 ] (Formula 1)

[0080] In this specification, the measurement under the measurement condition 1 and the measurement described later (measurement of in-plane phase difference, phase difference in the thickness direction, direction of the slow axis, visual reflectivity Y value, etc.) are performed in an atmosphere with a temperature of 23°C ± 5°C and a relative humidity of 40% to 65% unless otherwise specified. In addition, before each measurement, the measurement sample is exposed to the atmosphere for 30 minutes to 60 minutes.

[0081] In this specification, the a* value and the b* value are values ​​based on the L*a*b* colorimetric system standardized by the International Commission on Illumination (CIE) in 1976. The L*a*b* colorimetric system is adopted in JIS Z8781-4:2013.

[0082] Figure 1 1 is a cross-sectional view showing an embodiment of an optical film 100 of the present disclosure. Figure 1 As shown, the optical film 100 of the present disclosure has a low refractive index layer 30 on a plastic film 10 .

[0083] The optical film 100 of the present disclosure may have layers other than the plastic film 10 and the low refractive index layer 30. Examples of the layers other than the plastic film 10 and the low refractive index layer 30 include a hard coat layer, an antiglare layer, and a high refractive index layer. Figure 1 The optical film 100 has a hard coating layer 20 between a plastic film 10 and a low refractive index layer 30 .

[0084] In this specification, unless otherwise specified, "inside the plane of the plastic film" means "inside the plane in a direction perpendicular to the thickness direction of the plastic film". Figure 1 In the case of , the XY plane of the plastic film corresponds to the in-plane of the plastic film.

[0085] 《About measurement conditions 1》

[0086] Figure 2 This is a schematic diagram showing an example of measurement performed under measurement condition 1.

[0087] In condition 1, linearly polarized light L1 is incident from the surface of the optical film opposite to the low refractive index layer. Figure 2 In (a), an optical film 100 is disposed between the light source A1 and the detector A2. Figure 2 In (a), light L1 is emitted from a light source as linearly polarized light, and is incident on the surface of the optical film 100 opposite to the low refractive index layer 30 .

[0088] As the detector A2, a detector capable of detecting the normal transmitted light of the light L1 is used.

[0089] In the measurement condition 1, the light L1 is made incident on the optical film 100 with the angle between the slow axis of the plastic film and the vibration direction of the light L1 being fixed at 45 degrees. Figure 2 (b) is observed from the XY plane direction Figure 2 The slow axis of the plastic film, i.e., "S", and the vibration direction of the light L1, i.e., "V", are shown in (a). Figure 2 In (b), θ1 represents the angle between "S" which is the slow axis of the plastic film and "V" which is the vibration direction of the light L1. In measurement condition 1, θ1 is fixed to 45 degrees. In addition, "V" which is the vibration direction of the light L1 is actually inclined in the Z-axis direction.

[0090] In measurement condition 1, after θ1 is fixed at 45 degrees, the light L1 is incident on the optical film at an elevation angle of 50 degrees or more and 70 degrees or less with respect to the plane of the optical film. Figure 2 In (a), θ2 represents the elevation angle of the vibration direction of the light L1, namely “V”, with respect to the plane of the optical film as the reference (the plane of the optical film is set as the reference, namely 0 degrees). Figure 2 In (a), "F" represents the fast axis of the optical film. Figure 2 In (a), "F" as the fast axis is Figure 2 Extending in the Y-axis direction of (a).

[0091] In measurement condition 1, the elevation angle is varied by 2 degrees within a range of 50 degrees to 70 degrees, and the light L2 is measured at 11 elevation angles. Through the above measurement, the light L2 is measured at 11 measurement points. As a means for varying the elevation angle by 2 degrees within a range of 50 degrees to 70 degrees, for example, a means for tilting the optical film 100 with "F" as the fast axis as the rotation center can be cited.

[0092] The reason why the elevation angle is set to 50 degrees or more and 70 degrees or less in measurement condition 1 is that the Brewster angle of plastic films such as polyester films is taken into consideration. Rainbow flares of plastic films are easily observed strongly by naked eyes near the Brewster angle.

[0093] In the measurement condition 1, the light L2 is converted to the conditions of the C light source and the viewing angle of 2 degrees. By the above conversion, the influence of the light source can be eliminated from the obtained a* value and b* value.

[0094] Regarding the light L2 at the nth measurement point among the 11 measurement points, the a* value and the b* value of the L*a*b* colorimetric system are defined as a*n and b*n. Also, regarding the light L2 at the n+1th measurement point among the 11 measurement points, the a* value and the b* value of the L*a*b* colorimetric system are defined as a*n1 and b*n1. a*n, b*n, a*n1, and b*n1 are calculated from the converted light L2.

[0095] The above-mentioned measurement and calculation can be performed using, for example, a spectrophotometer with a product number of "V-7100" produced by JASCO Corporation.

[0096] In measurement condition 1, based on the measurement of the 11 measurement points, the sum of the square of the difference between a* and the square of the difference between b* at the adjacent measurement points is calculated. The sum is calculated at each of the 10 adjacent points, and ∑ T The Σ T It can be represented by the following formula 1.

[0097] ∑ T =∑[{a*na*n1} 2 +{b*nb*n1} 2 ] (Formula 1)

[0098] The optical film disclosed in the present invention is required to have a T The area that is greater than 0.04 and less than 0.20.

[0099] The Σ T The present inventors have found that the Σ T The present inventors have found that the lower the reflectivity of the optical film having a low refractive index layer on the plastic film, the easier it is to see the rainbow spots. T The smaller it is, the harder it is to see the rainbow flare. The rainbow flare is based on transmitted light.

[0100] Based on the above findings of the present inventors, it can be considered that the smaller the Σ T , the better the observability. However, the inventors found that the smaller the Σ T , the color tone changes more easily when viewed from an oblique direction, which leads to a problem of reduced color tone uniformity. In addition, the inventors have found that the main reason for the reduction in color tone uniformity is reflected light rather than transmitted light. T The Σ is within the specified range, which can eliminate the rainbow spots when observed with the naked eye and improve the uniformity of the color tone when observed from an oblique direction. T The value of Σ is greater than or equal to the specified value, which means that the reflectivity of the optical film having the low refractive index layer is increased. That is, the inventors have found that by deliberately increasing the reflectivity of the optical film having the low refractive index layer, the following problems can be solved: rainbow spots when observed with the naked eye are eliminated, and the uniformity of the color tone when observed from an oblique direction is improved. It can be considered that by making the above ΣT If Σ is greater than a predetermined value, the interference of reflected light from the optical film having a low refractive index layer can be suppressed, and the uniformity of the color tone when observed from an oblique direction can be improved. T If the refractive index of the low refractive index layer increases, the refractive index difference between the low refractive index layer and the layer in contact with the low refractive index layer tends to decrease, so the interference of the reflected light of the optical film is suppressed. As a result, it is considered that the uniformity of the color tone when observed from an oblique direction can be easily improved.)

[0101] In Σ T When Σ is less than 0.04, the interference of reflected light becomes strong, and the uniformity of color tone when observed from an oblique direction cannot be improved. T When Σ is greater than 0.20, the rainbow flare cannot be eliminated when observed with the naked eye. As mentioned above, the rainbow flare is based on the transmitted light. Therefore, by making Σ T When the value is greater than 0.04 and less than 0.20, the influence of both the transmitted light and the reflected light can be suppressed, and visibility can be made extremely good.

[0102] Σ T It is preferably 0.05 or more, and more preferably 0.06 or more. T It is preferably 0.15 or less, more preferably 0.10 or less, and further preferably 0.09 or less.

[0103] In the optical film of the present disclosure, for the Σ T The preferred range of can be listed as greater than 0.04 and less than 0.15, greater than 0.04 and less than 0.10, greater than 0.04 and less than 0.09, greater than 0.05 and less than 0.20, greater than 0.05 and less than 0.15, greater than 0.05 and less than 0.10, greater than 0.05 and less than 0.09, greater than 0.06 and less than 0.20, greater than 0.06 and less than 0.15, greater than 0.06 and less than 0.10, greater than 0.06 and less than 0.09, etc.

[0104] If the refractive index of the low refractive index layer is increased, there exists Σ T If the refractive index of the low refractive index layer is reduced, there is a tendency for Σ T If the refractive index of the low refractive index layer is reduced, the mechanical strength of the low refractive index layer tends to decrease. If the refractive index of the low refractive index layer is increased, the reflectivity of the optical film tends to increase. In order to make the reflectivity of the optical film within an appropriate range and to make the mechanical strength of the low refractive index layer good, the Σ T It is preferably 0.05 or more and 0.09 or less.

[0105] The above Σ can be easily reduced by “reducing the in-plane phase difference of the plastic film” and “reducing n2 / n1 which is a parameter related to the refractive index”. T In the case where there is a hard coat layer between the plastic film and the low refractive index layer, the Σ can be easily obtained by using a multifunctional (meth)acrylate oligomer having a molecular weight within a specified range as an ionizing radiation curable compound forming the hard coat layer. T is the range described.

[0106] In the optical film, Σ T The ratio of the region satisfying a value exceeding 0.04 and less than 0.20 is preferably 50% or more, more preferably 70% or more, further preferably 90% or more, and further preferably 100%.

[0107] Similarly, satisfying Σ T The ratio of the regions of various parameters other than those specified (Formula 2-1, Formula 2-2, in-plane phase difference, phase difference in the thickness direction, etc.) in the optical film is also preferably 50% or more, more preferably 70% or more, further preferably 90% or more, and further preferably 100%.

[0108] Regarding the optical film disclosed in the present invention, it is preferred that, based on the measurement of the 11 measurement points, when the maximum value of a* is defined as a*max, the minimum value of a* is defined as a*min, the maximum value of b* is defined as b*max, and the minimum value of b* is defined as b*min, the following Formulas 2-1 and 2-2 are satisfied.

[0109] a*max-a*min≤0.250 (Formula 2-1)

[0110] b*max-b*min≤0.350 (Formula 2-2)

[0111] By satisfying Formula 2-1 and Formula 2-2, the change in the transmission hue within the range of 50 degrees to 70 degrees can be made less noticeable. Therefore, by satisfying Formula 2-1 and Formula 2-2, rainbow flare can be more easily eliminated when observed with the naked eye.

[0112] If T If Σ is too small, the left side of equation 2-1 and equation 2-2 tends to become larger. This is probably because: T Become smaller, then the change of the optical distance of the low refractive index layer occupies the dominant position of color change. More specifically, it can be considered that it is due to: because the optical distance of the low refractive index layer changes linearly correspondingly with the angle, so a* value and b* value monotonically increase or monotonically decrease. Therefore, by satisfying formula 2-1 and formula 2-2, there is a tendency that the uniformity of the color tone when observing obliquely is also easy to become good.

[0113] The a*max-a*min in Formula 2-1 is more preferably 0.230 or less, further preferably 0.210 or less, and further preferably 0.200 or less. The lower limit of a*max-a*min in Formula 2-1 is not particularly limited, but is about 0.070. By setting a*max-a*min to be 0.070 or more, Σ T Become too big.

[0114] b*max-b*min in Formula 2-2 is more preferably 0.300 or less, more preferably 0.250 or less, more preferably 0.230 or less, more preferably 0.210 or less, and more preferably 0.200 or less. The lower limit of b*max-b*min in Formula 2-2 is not particularly limited, but is about 0.070. By setting b*max-b*min to be 0.070 or more, Σ T Become too big.

[0115] Preferred ranges of a*max-a*min in Formula 2-1 include 0.070 to 0.250, 0.070 to 0.230, 0.070 to 0.210, 0.070 to 0.200, and the like.

[0116] Preferred ranges of b*max-b*min in Formula 2-2 include 0.070 to 0.350, 0.070 to 0.300, 0.070 to 0.250, 0.070 to 0.230, 0.070 to 0.210, 0.070 to 0.200, and the like.

[0117] Formula 2-1 and Formula 2-2 can be easily satisfied by "reducing the in-plane phase difference of the plastic film" and "reducing n2 / n1 as a parameter related to the refractive index". In the case where there is a hard coating layer between the plastic film and the low refractive index layer, Formula 2-1 and Formula 2-2 can be easily satisfied by using a multifunctional (meth)acrylate oligomer with a molecular weight in a specified range as an ionizing radiation curable compound forming the hard coating layer.

[0118] a*max is preferably from -1.0 to 0, more preferably from -0.8 to -0.1.

[0119] b*max is preferably 0 or more and 2.0 or less, and more preferably 0.2 or more and 1.8 or less.

[0120] The optical film of the present disclosure preferably satisfies the following configuration.

[0121] Based on the measurements of the 11 measurement points, the sum of the square of the difference between the a* of the adjacent measurement points and the square of the difference between the b* of the adjacent measurement points is calculated. When the sum is defined as S, S can be expressed by the following formula 3. S is calculated at each of the 10 adjacent points, and the maximum value of S at the 10 points is defined as S MAX When S MAX It is preferably 0.010 or more and 0.050 or less.

[0122] S={a*na*n1} 2 +{b*nb*n1} 2 (Formula 3)

[0123] By making S MAX 0.050 or less can make the change of the transmission hue in the range of 50 degrees or more and 70 degrees or less more difficult to be felt. MAX When the value is 0.050 or less, rainbow flare during naked eye observation can be eliminated more easily.

[0124] If the reflectivity of the optical film having a low refractive index layer decreases, there is S MAX That is, if S MAX If S is too small, there is a tendency that the interference of reflected light from the optical film having the low refractive index layer is difficult to suppress. MAX When the ratio is 0.010 or more, the uniformity of the color tone when observed from an oblique direction can be easily improved.

[0125] S MAX The lower limit of S is more preferably 0.011 or more, and further preferably 0.012 or more. MAX The upper limit of is more preferably 0.040 or less, further preferably 0.030 or less, and further preferably 0.025 or less.

[0126] About S MAX The preferred range of can be listed as 0.010 to 0.040, 0.010 to 0.030, 0.010 to 0.025, 0.011 to 0.050, 0.011 to 0.040, 0.011 to 0.030, 0.011 to 0.025, 0.012 to 0.050, 0.012 to 0.040, 0.012 to 0.030, 0.012 to 0.025, etc.

[0127] By adding S MAX By setting the value to be 0.010 or more and 0.040 or less, it is possible to suppress the increase in b* and to suppress the loss of the high-quality feeling of the image display device.

[0128] S can be easily reduced by "reducing the in-plane phase difference of the plastic film" and "reducing n2 / n1, which is a parameter related to the refractive index". MAX In the case where there is a hard coat layer between the plastic film and the low refractive index layer, it is possible to easily make S MAX is the range described.

[0129] The optical film disclosed in the present invention is preferably: when the visual reflectivity Y value of the optical film is defined as R (%), the R and the Σ T The product is greater than or equal to 0.05 and less than or equal to 0.25.

[0130] By setting the product to be greater than or equal to 0.05 and less than or equal to 0.25, the effect of Σ T effect.

[0131] The product is more preferably 0.06 or more, and further preferably 0.07 or more. The product is more preferably 0.19 or less, further preferably 0.13 or less, and further preferably 0.11 or less. In particular, when the product is 0.11 or less, it is easy to make the image display device have a good sense of luxury.

[0132] Preferred ranges of the product include 0.05 or more and 0.19 or less, 0.05 or more and 0.13 or less, 0.05 or more and 0.11 or less, 0.06 or more and 0.25 or less, 0.06 or more and 0.19 or less, 0.06 or more and 0.13 or less, 0.06 or more and 0.11 or less, 0.07 or more and 0.25 or less, 0.07 or more and 0.19 or less, 0.07 or more and 0.13 or less, 0.07 or more and 0.11 or less, etc.

[0133] <Plastic film>

[0134] Examples of the resin component contained in the plastic film include polyester, polyimide, polyethersulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyetherketone, polymethyl methacrylate, polycarbonate, polyurethane, triacetylcellulose (TAC), and amorphous olefin (Cyclo-Olefin-Polymer: COP).

[0135] The plastic film is preferably a plastic film having a Brewster angle of 50 degrees or more and 70 degrees or less, and more preferably a plastic film having a Brewster angle of 55 degrees or more and 65 degrees or less. The elevation angle of the measurement condition 1 of the optical film disclosed in the present invention is 50 degrees or more and 70 degrees or less. Therefore, by setting the Brewster angle of the plastic film to 50 degrees or more and 70 degrees or less, the effect of the present invention can be easily exerted.

[0136] Examples of the resin having a Brewster angle of 50 degrees or more and 70 degrees or less include acrylic acid such as polymethyl methacrylate, polyester, TAC, and COP, etc. Among them, polyester is preferred because it is easy to improve mechanical strength.

[0137] Examples of polyester include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT). Among them, PET is preferred because it has low intrinsic birefringence and is easy to reduce in-plane phase difference.

[0138] The plastic film may contain additives such as ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, anti-gelling agents, inorganic particles, organic particles, pigments, dyes, antifouling agents, crosslinking agents and surfactants.

[0139] In order to improve the mechanical strength, the plastic film is preferably a stretched film, more preferably a biaxially stretched film. Biaxially stretched films are also preferred in that they have good tear resistance compared to uniaxially stretched films. Therefore, the plastic film is preferably a biaxially stretched plastic film.

[0140] In this specification, various embodiments such as "in-plane phase difference", "phase difference in thickness direction", "difference between the maximum value of D1 to D5 and the minimum value of D1 to D5" are listed as preferred embodiments of the plastic film. When the plastic film of the present disclosure is a biaxially stretched plastic film, it is more preferred to satisfy the preferred embodiments such as in-plane phase difference.

[0141] In order to easily suppress rainbow spots, the in-plane phase difference of the plastic film is preferably less than 2500nm. In addition, if the in-plane phase difference of the plastic film is reduced, the Σ T .

[0142] The in-plane phase difference of the plastic film is more preferably 2000 nm or less, more preferably 1500 nm or less, more preferably 1400 nm or less, more preferably 1250 nm or less, more preferably 1150 nm or less, more preferably 1100 nm or less, more preferably 1000 nm or less, more preferably 950 nm or less, more preferably 850 nm or less, more preferably 600 nm or less. By making the in-plane phase difference of the plastic film 2000 nm or less, the Σ T In addition, if the refractive index in the slow axis direction and the fast axis direction of the plastic film is different, the reflectivity of the optical film is different in the slow axis direction and the fast axis direction. In order to suppress the difference in reflectivity caused by direction, it is preferred to reduce the refractive index difference between the slow axis direction and the fast axis direction of the plastic film. Therefore, the in-plane phase difference of the plastic film is preferably less than 1250nm.

[0143] In order to improve the mechanical strength, the in-plane phase difference of the plastic film is preferably 20 nm or more, more preferably 100 nm or more, more preferably 300 nm or more, more preferably 400 nm or more, and more preferably 520 nm or more.

[0144] The preferred range of the in-plane phase difference of the plastic film is 20 nm to 2000 nm, 20 nm to 1500 nm, 20 nm to 1400 nm, 20 nm to 1250 nm, 20 nm to 1150 nm, 20 nm to 1100 nm, 20 nm to 1000 nm, 20 nm to 950 nm, 20 nm to 850 nm, 20 nm to 600 nm, 100 nm to 2000 nm, 100 nm to 1500 nm, and 1500 nm to 2000 nm. 100nm and below, 100nm and below 1400nm, 100nm and below 1250nm, 100nm and below 1150nm, 20nm and below 1100nm, 100nm and below 1000nm, 100nm and below 950nm, 100nm and below 850nm, 100nm and below 600nm, 300nm and below 2000nm, 300nm and below 1500nm, 300nm and below 1400nm, 300nm and below 1250nm, 300nm and above 11 50nm or less, 300nm or more and 1100nm or less, 300nm or more and 1000nm or less, 300nm or more and 950nm or less, 300nm or more and 850nm or less, 300nm or more and 600nm or less, 400nm or more and 2000nm or less, 400nm or more and 1500nm or less, 400nm or more and 1400nm or less, 400nm or more and 1250nm or less, 400nm or more and 1150nm or less, 400nm or more and 1100nm or less, 400nm or more and 1000nm or less, 400 nm and below 950nm, 400nm and above 850nm, 400nm and above 600nm, 520nm and above 2000nm, 520nm and above 1500nm, 520nm and above 1400nm, 520nm and above 1250nm, 520nm and above 1150nm, 520nm and below 1100nm, 520nm and above 1000nm, 520nm and above 950nm, 520nm and above 850nm, 520nm and below 600nm.

[0145] In order to make the in-plane retardation of the plastic film within the above range, it is preferred that the stretching ratio in the longitudinal direction (flow direction) and the stretching ratio in the transverse direction (width direction) be close to each other.

[0146] When the in-plane phase difference of the plastic film is in the range of 520 nm or more and 1400 nm or less, the suppression of rainbow spots and the above-mentioned Σ T The reduction of the reflectivity can be easily achieved, and the mechanical strength of the plastic film can be easily improved. In addition, when the in-plane phase difference of the plastic film is below 1250nm, the difference in reflectivity caused by the direction can be easily suppressed.

[0147] By setting the in-plane phase difference of the plastic film to be 50 nm or more, it is easy to suppress blackening. The reason is that a plastic film with an average in-plane phase difference of less than 50 nm hardly disturbs linearly polarized light, causing linearly polarized light to pass directly, while a plastic film with an average in-plane phase difference of more than 50 nm disturbs linearly polarized light. Blackening refers to the phenomenon that the entire surface becomes dark when light that has passed through the polarizer and the plastic film in sequence is observed through polarized sunglasses.

[0148] The phase difference (Rth) in the thickness direction of the plastic film is preferably 2000nm or more, more preferably 3000nm or more, further preferably 4000nm or more, and further preferably 5000nm or more. The upper limit of Rth is about 10000nm, preferably 8000nm or less, and more preferably 7000nm or less. By setting Rth to the above range, rainbow spots can be more easily suppressed. In order to suppress rainbow spots, it is particularly preferred to make Rth 5000nm or more. Furthermore, in order to make the pencil hardness of the plastic film good, Rth is preferably 5000nm or more. In order to easily suppress the breakage of the plastic film, Rth is preferably 10000nm or less.

[0149] The preferred range of Rth of the plastic film may be 2000 nm to 10000 nm, 2000 nm to 8000 nm, 2000 nm to 7000 nm, 3000 nm to 10000 nm, 3000 nm to 8000 nm, 3000 nm to 7000 nm, 4000 nm to 10000 nm, 4000 nm to 8000 nm, 4000 nm to 7000 nm, 5000 nm to 10000 nm, 5000 nm to 8000 nm, and 5000 nm to 7000 nm.

[0150] In order to make the Rth of the plastic film within the above range, it is preferred to increase the stretching ratio in the longitudinal direction (flow direction) and the transverse direction (width direction). By increasing the stretching ratio in the flow direction and the width direction, the refractive index in the thickness direction of the plastic film becomes smaller, so that the Rth can be easily increased.

[0151] By setting the in-plane phase difference and the phase difference in the thickness direction to be within the above ranges, the stretching degree of the plastic film can be made close to uniform biaxiality, and the mechanical strength of the plastic film can be easily improved.

[0152] When the refractive index in the slow axis direction is defined as nx, the refractive index in the fast axis direction is defined as ny, the refractive index in the thickness direction of the plastic film is defined as nz, and the thickness of the plastic film is defined as T [nm], the in-plane phase difference (Re) and the phase difference in the thickness direction (Rth) of the plastic film can be expressed by the following formulas i and ii. It should be noted that in this specification, the refractive index, the in-plane phase difference and the phase difference in the thickness direction refer to the values ​​at a wavelength of 590nm.

[0153] Re=(nx-ny)×T[nm] (Formula i)

[0154] Rth=((nx+ny) / 2-nz)×T[nm] (formula ii)

[0155] The direction of the slow axis, the in-plane phase difference, and the phase difference in the thickness direction can be measured, for example, by a product under the trade name of “RETS-100” manufactured by Otsuka Electronics Co., Ltd.

[0156] When measuring the in-plane phase difference or the like using a product of Otsuka Electronics Co., Ltd., trade name “RETS-100”, it is preferable to prepare for the measurement according to the following steps (A1) to (A4).

[0157] (A1) First, in order to stabilize the light source of RETS-100, leave it for more than 60 minutes after turning on the light source. Then, select the rotating analyzer method and select the θ mode (the mode for angular phase difference measurement and Rth calculation). By selecting this θ mode, the worktable becomes a tilting rotation worktable.

[0158] (A2) Next, the following measurement conditions are input into RETS-100.

[0159] (Measurement conditions)

[0160] Delay measurement range: rotating analyzer method

[0161] Measuring point diameter: φ5mm

[0162] Tilt angle range: 0°

[0163] ·Measurement wavelength range: above 400nm and below 800nm

[0164] Average refractive index of plastic film. For example, in the case of a PET film, N = 1.617. The average refractive index N of the plastic film can be calculated based on nx, ny, and nz by the formula (N = (nx + ny + nz) / 3).

[0165] Thickness: Thickness measured separately using SEM or optical microscope

[0166] (A3) Next, background data is obtained without placing a sample in the device. The device is set as a closed system, and the closed system is implemented every time the light source is turned on.

[0167] (A4) Then, a sample is set on a stage within the device and measurement is performed.

[0168] For the in-plane phase difference and the phase difference in the thickness direction, and the direction of the slow axis, it is preferred to cut a sample of 50 mm in length and 50 mm in width from the plastic film, and find the average of the measured values ​​at 5 locations of the sample. The 5 measurement locations are 1 location in the center of the sample, and 4 locations (10 mm from each of the four corners of the sample toward the center of the sample) Figure 5 5 locations of the black dots).

[0169] The in-plane phase differences measured at the five locations of the above sample are defined as Re1, Re2, Re3, Re4 and Re5, and the phase differences in the thickness direction measured at the five locations of the above sample are defined as Rth1, Rth2, Rth3, Rth4 and Rth5.

[0170] The average value of Re1 / Rth1, Re2 / Rth2, Re3 / Rth3, Re4 / Rth4 and Re5 / Rth5 of the plastic film is preferably 0.20 or less.

[0171] A small ratio of the in-plane phase difference to the phase difference in the thickness direction (Re / Rth) means that the biaxial stretching of the plastic film is close to equal biaxiality. Therefore, by making Re / Rth less than 0.20, the mechanical strength of the plastic film can be improved. Re / Rth is more preferably less than 0.18, and further preferably less than 0.16. The lower limit of Re / Rth is about 0.01.

[0172] The Re / Rth of a completely uniaxially stretched plastic film is 2.0. A general-purpose uniaxially stretched plastic film is also slightly stretched in the flow direction. Therefore, the Re / Rth of a general-purpose uniaxially stretched plastic film is about 1.0.

[0173] Re1 / Rth1, Re2 / Rth2, Re3 / Rth3, Re4 / Rth4 and Re5 / Rth5 are each preferably 0.20 or less, more preferably 0.18 or less, and further preferably 0.16 or less. The lower limits of these ratios are approximately 0.01.

[0174] In the case where the plastic film has a layer or film that affects the values ​​of the in-plane phase difference and the phase difference in the thickness direction, these layers or films may be peeled off and then the in-plane phase difference and the phase difference in the thickness direction of the plastic film may be measured. It should be noted that the layer formed by coating generally does not affect the value difference of the in-plane phase difference and the phase difference in the thickness direction.

[0175] As a means for peeling off the layer and film which affect the value of the in-plane retardation and the retardation in the thickness direction, the following means can be mentioned.

[0176] <Methods of stripping>

[0177] Immerse a sample of 5 cm square or more in warm water at 80°C or more and 90°C or less for 5 minutes. Then, take out the sample from the warm water and leave it at room temperature for more than 10 minutes. Then, immerse it in warm water for another 5 minutes. Take out the sample from the warm water. Make an incision in the sample with a knife or the like. In addition, a method of peeling off the layer and the film from the incision as a starting point can be cited.

[0178] In the above-mentioned means, it is preferable to immerse the sample in warm water in a state where the edge of the sample is attached to a metal frame or the like.

[0179] The plastic film preferably satisfies the following condition A.

[0180] <Condition A>

[0181] The directions of the slow axis are measured at 5 locations of the sample. When the angles formed between any one side of the sample and the directions of the slow axis of each measurement location are defined as D1, D2, D3, D4, and D5, respectively, the difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is greater than 1.5 degrees.

[0182] If the slow axis of the plastic film is uniformly oriented, the Σ T The tendency of rainbow spots to become larger and easier to observe is greater. On the other hand, if the slow axis of the plastic film is biased, the rainbow spots become blurred and difficult to observe. Therefore, by satisfying condition A, it is possible to easily suppress the situation where rainbow spots are observed with the naked eye. In other words, by satisfying condition A, the Σ T The range is easily satisfied.

[0183] The general stretched plastic film is designed so that the direction of the slow axis does not deviate. However, as described above, rainbow flare can be easily suppressed by deliberately deviating the direction of the slow axis of the plastic film. In addition, even if the slow axis fluctuates in a larger area, the effect of suppressing rainbow flare is small, but by fluctuating the slow axis in a relatively small area such as 50 mm in the vertical direction and 50 mm in the horizontal direction, rainbow flare can be easily suppressed.

[0184] In this specification, “calculating the Σ T The direction of the slow axis at the time of the experiment is the average direction of the slow axis at 5 locations of the sample.

[0185] In condition A, any one side of the sample that serves as a reference for the angle formed with the slow axis direction may be any of the longitudinal side and the lateral side of the sample as long as the same side is used as a reference in all D1 to D5.

[0186] Furthermore, a plastic film satisfying the condition A is preferred in that the folding resistance of the plastic film can be improved.

[0187] On the other hand, for a general-purpose oriented film that does not satisfy condition A and has the same slow axis, the film breaks after the bending test or a strong crease remains. Specifically, for a uniaxially stretched film such as Patent Document 1, the film breaks when the bending test is performed along the slow axis, and a strong crease remains when the bending test is performed in a direction perpendicular to the slow axis. In addition, for a general-purpose biaxially stretched film, a strong crease remains when the bending test is performed in a direction perpendicular to the slow axis.

[0188] A plastic film satisfying condition A is preferred in that it is possible to suppress the occurrence of folds remaining or breakage after a bending test regardless of the direction of the fold.

[0189] Furthermore, a plastic film satisfying condition A is preferred in that microcracks of the plastic film after a bending test can be easily suppressed.

[0190] In addition, a plastic film satisfying condition A is preferable in that even if the pencil hardness is high, the bending resistance of the plastic film can be easily improved.

[0191] The difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is preferably 2.0 degrees or more, more preferably 3.0 degrees or more, and further preferably 3.5 degrees or more.

[0192] It should be noted that when the difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is too large, there is a tendency for the orientation of the plastic film to be reduced and the mechanical strength to be reduced. Therefore, the difference is preferably 20.0 degrees or less, more preferably 17.0 degrees or less, more preferably 15.0 degrees or less, more preferably 10.0 degrees or less, more preferably 9.0 degrees or less, and more preferably 8.0 degrees or less.

[0193] In condition A, the preferred range of the difference between the maximum value and the minimum value of D1 to D5 is, for example, 1.5 degrees to 20.0 degrees, 2.0 degrees to 20.0 degrees, 3.0 degrees to 20.0 degrees, 3.5 degrees to 20.0 degrees, 1.5 degrees to 17.0 degrees, 2.0 degrees to 17.0 degrees, 3.0 degrees to 17.0 degrees, 3.5 degrees to 17.0 degrees, 1.5 degrees to 15.0 degrees, 2.0 degrees to 15.0 degrees, 3.0 degrees to 1 5.0 degrees or less, 3.5 degrees or more and 15.0 degrees or less, 1.5 degrees or more and 10.0 degrees or less, 2.0 degrees or more and 10.0 degrees or less, 3.0 degrees or more and 10.0 degrees or less, 3.5 degrees or more and 10.0 degrees or less, 1.5 degrees or more and 9.0 degrees or less, 2.0 degrees or more and 9.0 degrees or less, 3.0 degrees or more and 9.0 degrees or less, 3.5 degrees or more and 9.0 degrees or less, 1.5 degrees or more and 8.0 degrees or less, 2.0 degrees or more and 8.0 degrees or less, 3.0 degrees or more and 8.0 degrees or less, 3.5 degrees or more and 8.0 degrees or less.

[0194] D1 to D5 of the plastic film are preferably 5 to 30 degrees, or 60 to 85 degrees, more preferably 7 to 25 degrees, or 65 to 83 degrees, and further preferably 10 to 23 degrees, or 67 to 80 degrees.

[0195] By setting D1 to D5 to 5 degrees or more or 85 degrees or less, it is easy to suppress the darkening when observing with polarized sunglasses. In addition, by setting D1 to D5 to 30 degrees or less or 60 degrees or more, it is easy to suppress the reduction in mechanical strength due to the low orientation of the plastic film.

[0196] The plastic film may be in sheet form or in roll form. In either case, a sample of 50 mm in length by 50 mm in width may be cut out from any position of the plastic film as long as the following criteria are followed.

[0197] However, in the case where the longitudinal and transverse directions of the sheet and the roll can be confirmed, the sample is cut out along the confirmed longitudinal and transverse directions. For example, in the case of a roll, the flow direction (MD direction) of the roll can be regarded as the longitudinal direction, and the width direction (TD direction) of the roll can be regarded as the transverse direction. In the case where the flow direction and width direction of the sheet can be confirmed, the flow direction can be regarded as the longitudinal direction, and the width direction can be regarded as the transverse direction. In the case where it is difficult to confirm the flow direction and width direction of the sheet, if the sheet is a rectangle or a square, it is sufficient to confirm the longitudinal and transverse directions using the four sides that constitute the rectangle or the square. In the case where it is difficult to confirm the flow direction and width direction of the sheet, if the sheet is a shape other than a rectangle and a square (a circle, a triangle, etc.), it is sufficient to draw a rectangle or a square with the largest area that does not exceed the outer frame shape of the sheet, and use the sides of the drawn rectangle or square to confirm the longitudinal and transverse directions.

[0198] Samples are cut out by removing 10 mm from the corners of sheets and rolls. In the case of sheet form, for samples of 50 mm in length and 50 mm in width, the four corners of the sheet are cut out first, and the center of the sheet is cut out second. Then, after cutting out samples from the four corners and the center, if there is an area exceeding 50 mm in length and 50 mm in width left, sampling can be performed by cutting out a maximum of 50 mm in length and 50 mm in width from the remaining area.

[0199] It should be noted that, when a plurality of samples of 50 mm in length and 50 mm in width can be collected from a sheet of plastic film, the proportion of samples satisfying condition A among the plurality of samples is preferably 50% or more, more preferably 70% or more, further preferably 90% or more, and further preferably 100%. The same applies to other parameters such as in-plane phase difference, phase difference in the thickness direction, and Re / Rth.

[0200] Regarding a rolled plastic film, various physical properties tend to change in the width direction, but various physical properties are almost the same in the flow direction. Therefore, when a sample collected from a specified position in the width direction of the roll satisfies the specified physical properties such as condition A, the same position in the width direction can be assumed to satisfy the specified physical properties in the entire flow direction of the roll.

[0201] The plastic film preferably does not produce cracks or breaks after the folding test shown in the embodiment is performed 100,000 times (more preferably after 300,000 times). In addition, with respect to the plastic film, after the folding test shown in the embodiment is performed 100,000 times (more preferably after 300,000 times), the measurement sample is placed on a horizontal table, and at this time, the angle at which the end of the sample is tilted from the table is preferably less than 20 degrees, more preferably less than 15 degrees. The tilting angle of the end of the sample is less than 15 degrees, which means that wrinkles caused by folding are difficult to produce. In addition, for any direction of the average in the direction of the slow axis and the average in the direction of the fast axis of the plastic film, it is preferred to show the aforementioned results (no cracks, breaks, and wrinkles caused by folding. The tilting angle of the end of the sample after the test is less than 20 degrees).

[0202] It should be noted that, when a uniaxially stretched plastic film is subjected to a folding test, it breaks in the stretching direction and leaves strong folds in the direction perpendicular to the stretching direction. Therefore, among the stretched films, biaxially stretched plastic films are also preferred.

[0203] The lower limit of the thickness of the plastic film is preferably 10 μm or more, more preferably 15 μm or more, more preferably 21 μm or more, more preferably 25 μm or more, more preferably 30 μm or more, and the upper limit is preferably 200 μm or less, more preferably 180 μm or less, more preferably 150 μm or less, more preferably 100 μm or less, more preferably 80 μm or less, more preferably 60 μm or less, more preferably 50 μm or less.

[0204] By making the thickness 10 μm or more, it is easy to make the mechanical strength good. In addition, in order to reduce the moisture permeability and prolong the life of the polarizing plate, the thickness is preferably 21 μm or more, and more preferably 30 μm or more. In addition, if the panel size is a large panel of 50 inches or more, when the panel is vertically erected, deformation caused by the dead weight of the plastic film is likely to occur. In order to suppress the deformation, the thickness of the plastic film is preferably 30 μm or more.

[0205] By setting the thickness to 200 μm or less, the in-plane phase difference of the plastic film can be easily set to 2500 nm or less. In order to reduce the thickness of the panel and the image display device, the thickness of the plastic film is preferably 60 μm or less, more preferably 50 μm or less.

[0206] The thickness of the plastic film is preferably in a range of, for example, 10 μm to 200 μm, 15 μm to 200 μm, 21 μm to 200 μm, 25 μm to 200 μm, 30 μm to 200 μm, 10 μm to 180 μm, 15 μm to 180 μm, 21 μm to 180 μm, 25 μm to 180 μm, 30 μm to 180 μm, 10 μm to 150 μm, 15 μm to 150 μm, 21 μm to 150 μm, 25 μm to 150 μm, 30 μm to 150 μm, 10 μm to 100 μm, 15 μm to 1 00μm or less, 21μm or more and 100μm or less, 25μm or more and 100μm or less, 30μm or more and 100μm or less, 10μm or more and 80μm or less, 15μm or more and 80μm or less, 21μm or more and 80μm or less, 25μm or more and 80μm or less, 30μm or more and 80μm or less, 10μm or more and 60μm or less, 15μm or more and 60μm or less, 21μm or more and 60μm or less, 25μm or more and 60μm or less, 30μm or more and 60μm or less, 10μm or more and 50μm or less, 15μm or more and 50μm or less, 21μm or more and 50μm or less, 25μm or more and 50μm or less, 30μm or more and 50μm or less.

[0207] The haze of the plastic film in accordance with JIS K7136:2000 is preferably 3.0% or less, more preferably 2.0% or less, further preferably 1.5% or less, and still further preferably 1.0% or less.

[0208] The total light transmittance of the plastic film in accordance with JIS K7361-1:1997 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more.

[0209] <Erosion rate>

[0210] Regarding the plastic film, the average value of the erosion rate from the surface of the plastic film to a depth of 20 μm is defined as E. 0-20 When E 0-20 It is preferably 1.4 μm / g or more.

[0211] In this manual, E is measured under the following measurement conditions. 0-20 .

[0212] <Measurement conditions>

[0213] The following test liquid is stored in a container: the test liquid is a mixture of pure water, a dispersion liquid, and spherical silica whose average particle size is within ±8% based on 4.2 μm in a mass ratio of 968:2:30. The test liquid in the container is delivered to a nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and a predetermined amount of the test liquid is vertically sprayed from the spray hole at the end of the nozzle to the first surface of the plastic film, so that the spherical silica in the test liquid collides with the plastic film. The cross-sectional shape of the nozzle is a square of 1 mm×1 mm, and the distance between the spray hole and the plastic film is 4 mm. In addition, the flow rate of the test liquid and the compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are predetermined values ​​adjusted by the calibration described later.

[0214] After a predetermined amount of the test liquid is sprayed, the spraying of the test liquid is temporarily stopped.

[0215] After the injection of the test liquid was temporarily stopped, the cross-sectional profile of the portion of the plastic film that collided with the spherical silica in the test liquid was measured.

[0216] An operation consisting of the following three steps as one cycle is performed until the depth of the cross-sectional profile exceeds 20 μm: a step of ejecting a predetermined amount of the test liquid from the ejection port; a step of temporarily stopping the ejection of the test liquid after ejecting the predetermined amount of the test liquid; and a step of measuring the cross-sectional profile after temporarily stopping the ejection of the test liquid. Then, in each cycle until the depth of the cross-sectional profile reaches 20 μm, the erosion rate (μm / g) of the plastic film is calculated. The erosion rate of the plastic film in each cycle until the depth of the cross-sectional profile reaches 20 μm is averaged to calculate the E 0-20 .

[0217] <Correction>

[0218] The test liquid is stored in the container. The test liquid in the container is delivered to the nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and any amount of the test liquid is vertically sprayed from the spray hole at the end of the nozzle to the acrylic plate with a thickness of 2 mm, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm.

[0219] After an arbitrary amount of the test liquid is sprayed, the spraying of the test liquid is temporarily stopped. After the spraying of the test liquid is temporarily stopped, a cross-sectional profile of a portion of the acrylic plate that collides with the spherical silica in the test liquid is measured.

[0220] The corrosion rate (μm / g) of the acrylic plate was calculated by dividing the depth (μm) of the cross-sectional profile by the arbitrary amount (g).

[0221] The erosion rate of the acrylic plate is set as a qualified condition within the range of ±5% based on 1.88 (μm / g), and the flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted and corrected in such a way that the erosion rate of the acrylic plate falls within the range.

[0222] Below, citing Figure 7 The measurement conditions of the erosion rate and the technical significance of the erosion rate calculated under the measurement conditions are explained. Figure 7 As such an apparatus for measuring the erosion rate, for example, there can be mentioned an MSE test apparatus with a product number of "MSE-A203" produced by Palmeso Co., Ltd., and the like.

[0223] Under the erosion rate measurement conditions disclosed herein, first, a test liquid is placed in a container (11): the test liquid is a mixture of pure water, a dispersant, and spherical silica having an average particle size within ±8% of 4.2 μm in a mass ratio of 968:2:30. The test liquid is preferably stirred in the container (11).

[0224] There are no particular limitations on the dispersant as long as it can disperse the spherical silica. Examples of the dispersant include a product under the trade name "Demol N" manufactured by Wako Pure Chemical Industries, Ltd.

[0225] The “average particle size is within ±8% based on 4.2 μm” means, in other words, that the average particle size is 3.864 μm or more and 4.536 μm or less.

[0226] In the measurement conditions of the erosion rate in the present specification, the “average particle size of spherical silica” is an average particle size (so-called “median particle size”) measured as a volume average value d50 in particle size distribution measurement based on a laser diffraction method.

[0227] The spherical silica is preferably: in the result of the particle size distribution measurement, when the frequency of the particle size with the maximum frequency is standardized to 100, the width of the particle size with a frequency of 50 is within ±10% based on 4.2μm. Regarding the "width of the particle size with a frequency of 50", when "the particle size with a frequency of 50, which is in the positive direction of the particle size with a frequency of 100, is defined as X", and "the particle size with a frequency of 50, which is in the negative direction of the particle size with a frequency of 100, is defined as Y", the "width of the particle size with a frequency of 50" is represented by "XY (μm)". It should be noted that in this specification, the "width of the particle size with a frequency of 50" is sometimes referred to as the "full width at half maximum of the particle size distribution".

[0228] As spherical silica having an average particle size within ±8% of 4.2 μm, there can be cited the model “MSE-BS-5-3” designated by Palmeso Co., Ltd. As spherical silica conforming to the model “MSE-BS-5-3” designated by Palmeso Co., Ltd., there can be cited, for example, the product number “BS5-3” of Potters-Ballotini Co., Ltd.

[0229] The test liquid in the container is fed into the nozzle (51). The test liquid can be fed to the nozzle through a test liquid pipe (21), for example. A flow meter (31) for measuring the flow rate of the test liquid is preferably arranged between the container (11) and the nozzle (51). The flow rate of the test liquid is set to a value adjusted by the calibration.

[0230] exist Figure 7 In the invention, the nozzle (51) is arranged in a housing (52) constituting a spraying portion (50).

[0231] Compressed air is delivered to the nozzle (51). The compressed air is delivered to the nozzle, for example, through a compressed air pipe (22). In the nozzle, the compressed air is delivered to a position that is preferably upstream of the position where the test liquid is delivered. The upstream side refers to the side of the nozzle that is away from the injection hole.

[0232] Preferably, a flow meter (32) for measuring the flow rate of compressed air before the compressed air reaches the nozzle (51) and a pressure gauge (42) for measuring the pressure of the compressed air are provided. The compressed air can be supplied by an air compressor (not shown) or the like.

[0233] The flow rate and pressure of the compressed air are values ​​adjusted by the above-mentioned calibration.

[0234] When compressed air is supplied to the nozzle (51), the test liquid is accelerated while being mixed by the compressed air. The accelerated test liquid is ejected from the ejection hole at the end of the nozzle (51) and collides vertically with the plastic film (70). The plastic film is mainly abraded by the spherical silica particles in the test liquid.

[0235] A pressure gauge (41) for measuring the pressure of the test liquid in the nozzle is preferably arranged in the nozzle (51). Preferably, the pressure gauge (41) is located downstream of the position where the compressed air is fed and the position where the test liquid is fed.

[0236] The pressure of the test fluid in the nozzle (51) is a value adjusted by the above calibration.

[0237] The test liquid sprayed from the spray hole at the end of the nozzle (51) is mixed with air and sprayed in a mist form. Therefore, the collision pressure of the spherical silica particles on the plastic film can be reduced. Therefore, the amount of wear of the plastic film caused by one spherical silica particle can be suppressed to a trace amount. Figure 8 Schematic diagram of a state in which a plastic film (70) is worn by a test liquid containing pure water (A1) and spherical silica (A2) ejected from an ejection unit (50). Figure 8 In the figure, reference numeral A3 represents air, and reference numeral A4 represents the plastic film after wear.

[0238] In addition, since the test liquid contains water with excellent cooling effect, the deformation and deterioration of the plastic film caused by the heat during collision can be substantially eliminated. In other words, abnormal wear of the plastic film can be substantially eliminated. In addition, water also has the function of cleaning the surface of the worn plastic film, thereby achieving stable wear. In addition, water has the function of accelerating the spherical silica particles or controlling the fluidity of the test liquid.

[0239] In addition, since a large number of spherical silica particles collide with the plastic film, the influence of subtle differences in physical properties of individual spherical silica particles can be eliminated.

[0240] Furthermore, the measurement conditions disclosed in the present invention are values ​​after the flow rate of the test liquid supplied to the nozzle, the flow rate of the compressed air supplied to the nozzle, the pressure of the compressed air supplied to the nozzle, and the pressure of the test liquid in the nozzle are adjusted by the calibration, and the cross-sectional shape of the nozzle is determined to be a 1 mm × 1 mm square, and the distance between the injection hole and the plastic film is determined to be 4 mm, thereby determining the factors that affect the wear amount of the plastic film. The distance is Figure 7 The distance shown by "d" refers to the vertical distance between the spray hole at the end of the nozzle and the plastic film.

[0241] As can be seen from the above, the measurement conditions of the present disclosure can be said to be measurement conditions that can form statistically stable wear marks on the plastic film.

[0242] The plastic film (70) may be mounted on the sample mounting table (81) of the measuring device (100). The plastic film (70) is preferably mounted on the sample mounting table (81) via a support (82) such as a stainless steel plate.

[0243] The test liquid sprayed onto the plastic film (70) is preferably recovered by the receiver (12) and returned to the container (11) through the return pipe (23). A return pump (24) is preferably arranged between the receiver (12) and the return pipe (23).

[0244] The measurement conditions of the present disclosure require that the injection of the test liquid is temporarily stopped after a predetermined amount of the test liquid is injected, and that the cross-sectional profile of the portion of the plastic film that collides with the spherical silica in the test liquid is measured after the injection of the test liquid is temporarily stopped.

[0245] The cross-sectional profile refers to the cross-sectional shape of the plastic film worn by the test fluid. The plastic film is mainly worn by the spherical silica particles in the test fluid.

[0246] The corresponding cross-sectional profile can be measured by a cross-sectional profile acquisition unit (60) such as a stylus-type surface shape measuring device or a laser interferometer-type surface shape measuring device. It should be noted that the cross-sectional profile acquisition unit (60) is usually arranged at a position separated from the plastic film (70) when the test liquid is sprayed. Therefore, it is preferred that at least one of the plastic film (70) and the cross-sectional profile acquisition unit (60) is movable.

[0247] The cross-sectional profile measuring means of the MSE test device with the product number "MSE-A203" of Palmeso Co., Ltd. is a stylus type.

[0248] Furthermore, under the measurement conditions of the present disclosure, an operation consisting of the following three steps as one cycle is performed until the depth of the cross-sectional profile exceeds 20 μm: a step of ejecting a specified amount of test liquid from an ejection port; a step of temporarily stopping the ejection of the test liquid after ejecting the specified amount of test liquid; and a step of measuring the cross-sectional profile after temporarily stopping the ejection of the test liquid.

[0249] By performing the above operation, the erosion rate of the plastic film in each cycle can be measured, and further, the variation in the erosion rate of the plastic film can be calculated.

[0250] The above cycle may be continued even after the depth of the cross-sectional profile exceeds 20 μm, but it is preferably terminated when the depth of the cross-sectional profile exceeds 20 μm. The reason for performing the measurement "from the surface of the plastic film to a depth of 20 μm" is that the physical properties of the plastic film tend to change near the surface, while the physical properties of the plastic film become more stable toward the inside.

[0251] In this specification, the erosion rate of each cycle can be calculated by dividing the depth (μm) of the cross-sectional profile advanced in each cycle by the injection amount (g) of the test liquid in each cycle. The depth (μm) of the cross-sectional profile of each cycle is the depth of the deepest position of the cross-sectional profile of each cycle.

[0252] The injection amount of the test liquid in each cycle is "fixed" in principle, but may vary slightly in each cycle.

[0253] The injection amount of the test liquid in each cycle is not particularly limited, but the lower limit is preferably 0.5 g or more, more preferably 1.0 g or more, and the upper limit is preferably 3.0 g or less, more preferably 2.0 g or less.

[0254] Under the measurement conditions disclosed herein, the erosion rate (μm / g) was calculated in each cycle until the depth of the cross-sectional profile reached 20 μm. Then, the erosion rate in each cycle until the depth of the cross-sectional profile reached 20 μm was averaged to calculate E 0-20 .

[0255] The cycles were performed until the depth of the cross-sectional profile exceeded 20 μm, but the data for the cycles where the depth of the cross-sectional profile exceeded 20 μm were removed from the data used to calculate E 0-20 data deviation.

[0256] Generally speaking, a plastic film is easily damaged if it is soft, and is difficult to be damaged if it is hard. PICODENTOR The values ​​obtained by the evaluation including the depth direction (Martens hardness, indentation hardness, elastic recovery work, etc.) are used as indicators of pencil hardness. However, the parameters such as Martens hardness, indentation hardness, elastic recovery work, etc. may not be used as indicators of pencil hardness.

[0257] In addition, the strength of plastic films tends to increase when stretched. Specifically, uniaxially stretched plastic films tend to have better pencil hardness than unstretched plastic films, and biaxially stretched plastic films tend to have better pencil hardness than uniaxially stretched plastic films. However, even biaxially stretched plastic films may have insufficient pencil hardness.

[0258] The inventors studied the erosion rate as an index of the pencil hardness of plastic films. As described above, a plastic film is easily damaged when it is soft, and is difficult to be damaged when it is hard. Therefore, it is believed that a small erosion rate can make the pencil hardness good. However, the inventors found that by increasing the erosion rate (E 0-20 ) increases to 1.4 μm / g or more, the plastic film can have a good pencil hardness. In addition, the inventors have found that the erosion rate of the plastic film is likely to be larger for a biaxially stretched plastic film than for a uniaxially stretched plastic film, and that the quality of the pencil hardness of the biaxially stretched plastic film can be determined by the erosion rate.

[0259] The reason why the erosion rate of the plastic film and the pencil hardness are correlated is considered to be as follows.

[0260] As described above, under the measurement conditions disclosed herein, the test liquid containing water and spherical silica is sprayed in a mist form after being mixed with air. Therefore, it can be considered that the collision pressure of the spherical silica particles on the plastic film is suppressed to be relatively low. Therefore, in the case where the plastic film is soft, the stress when the spherical silica collides with the plastic film is easily dispersed, so the plastic film is not easily worn, and the erosion rate becomes low. On the other hand, it can be considered that in the case where the plastic film is hard, the stress when the spherical silica collides with the plastic film is difficult to disperse, so the plastic film is easily worn, and the erosion rate becomes high.

[0261] In addition, it is believed that the difference in the erosion rate in the biaxially stretched plastic film is caused by the difference in the degree of elongation of the molecular chain and the difference in the degree of orientation of the molecules. For example, in principle, the molecules of the biaxially stretched plastic film are stretched in the plane, but sometimes there are molecules that are not fully stretched locally in the plane. In this way, it is believed that if the proportion of the molecules that are not fully stretched locally in the plane increases, the biaxially stretched plastic film becomes partially soft, thereby reducing the erosion rate.

[0262] In addition, it is considered that even biaxially stretched plastic films with the same in-plane phase difference may show different erosion rates due to differences in local molecular orientation. Conversely, even biaxially stretched plastic films with the same erosion rate may show different in-plane phase differences due to differences in the ratio of the stretching ratio in the flow direction to the stretching ratio in the width direction.

[0263] In order to make the pencil hardness of the plastic film good, E 0-20 It is preferably 1.4 μm / g or more, more preferably 1.6 μm / g or more, more preferably 1.8 μm / g or more, more preferably 1.9 μm / g or more, and more preferably 2.0 μm / g or more.

[0264] As described above, it can be considered that if the proportion of molecules that are not fully stretched locally in the plane increases, the erosion rate decreases. In other words, it can be considered that if the erosion rate is high, the proportion of molecules that are not fully stretched locally in the plane decreases. Therefore, by increasing E 0-20 When the molecular weight is 1.4 μm / g or more, it is possible to easily suppress the occurrence of wrinkles on the plastic film in a high temperature environment.

[0265] In order to make the plastic film not easy to break, E 0-20 It is preferably 3.0 μm / g or less, more preferably 2.5 μm / g or less, and further preferably 2.2 μm / g or less.

[0266] Even if E 0-20 The same value of E may lead to different characteristics of plastic films when the in-plane retardation and other factors are different. 0-20 , but when the in-plane phase difference exceeds 1450 nm, creases may remain on the plastic film or the plastic film may break when the plastic film is folded.

[0267] In addition, for E 0-20 In the case of a plastic film having a thickness of less than 1.4 μm / g, even if a cured film having high hardness is formed on the plastic film, the pencil hardness of the cured film may not be good due to insufficient hardness of the plastic film.

[0268] For E 0-20 Embodiments of the preferred numerical range of can be listed, for example, 1.4 μm / g or more and 3.0 μm / g or less, 1.4 μm / g or more and 2.5 μm / g or less, 1.4 μm / g or more and 2.2 μm / g or less, 1.5 μm / g or more and 3.0 μm / g or less, 1.5 μm / g or more and 2.5 μm / g or less, 1.5 μm / g or more and 2.2 μm / g or less, 1.6 μm / g or more and 3.0 μm / g or less, 1.6 μm / g or more and 2.5 μm / g or less, 1.6 μm / g or more and 2.5 μm / g or less, And 2.2μm / g or less, 1.8μm / g or more and 3.0μm / g or less, 1.8μm / g or more and 2.5μm / g or less, 1.8μm / g or more and 2.2μm / g or less, 1.9μm / g or more and 3.0μm / g or less, 1.9μm / g or more and 2.5μm / g or less, 1.9μm / g or more and 2.2μm / g or less, 2.0μm / g or more and 3.0μm / g or less, 2.0μm / g or more and 2.5μm / g or less, 2.0μm / g or more and 2.2μm / g or less.

[0269] The plastic film has two planes, the front side and the back side. The plastic film is preferably: 0-20 and E measured from the other plane side 0-20For a general plastic film, the erosion rate measured from one flat surface side is substantially the same as the erosion rate measured from the other flat surface side.

[0270] The calibration is performed before measuring the above-mentioned erosion rate.

[0271] For example, the correction can be performed as follows.

[0272] <Correction>

[0273] The test liquid is stored in the container. The test liquid in the container is delivered to the nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and any amount of the test liquid is vertically sprayed from the spray hole at the end of the nozzle to the acrylic plate with a thickness of 2 mm, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm.

[0274] After an arbitrary amount of the test liquid is sprayed, the spraying of the test liquid is temporarily stopped. After the spraying of the test liquid is temporarily stopped, a cross-sectional profile of a portion of the acrylic plate that collides with the spherical silica in the test liquid is measured.

[0275] The corrosion rate (μm / g) of the acrylic plate was calculated by dividing the depth (μm) of the cross-sectional profile by the arbitrary amount (g).

[0276] The erosion rate of the acrylic plate is set as a qualified condition within the range of ±5% based on 1.88 (μm / g). The flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted and corrected so that the erosion rate of the acrylic plate falls within the range.

[0277] The test solution used in the calibration is the same as the test solution used under the measurement conditions to be performed later.

[0278] In addition, the measuring device used for calibration is the same as the measuring device used under the measurement conditions to be performed later.

[0279] The difference between the calibration and the measurement conditions to be performed later is that, for example, an acrylic plate with a thickness of 2 mm as a standard sample is used as a sample in the calibration, whereas a plastic film is used as a sample in the measurement conditions.

[0280] The acrylic plate with a thickness of 2 mm as the standard sample is preferably a polymethyl methacrylate plate (PMMA plate). In addition, for the acrylic plate with a thickness of 2 mm as the standard sample, when the average value of the erosion rate of the acrylic plate measured under the following measurement condition A is defined as AcE, AcE is preferably 1.786 μm / g or more and 1.974 μm / g or less. In addition, as the spherical silica in the following measurement condition A, the spherical silica with the model "MSE-BS-5-3" specified by Palmeso Co., Ltd. can be cited. Examples of spherical silica conforming to the model “MSE-BS-5-3” designated by Palmeso Co., Ltd. include a product numbered “BS5-3” produced by Potters-Ballotini Co., Ltd.

[0281] <Measurement Condition A>

[0282] The following test liquid is stored in a container: the test liquid is a mixture of pure water, a dispersant, and spherical silica with an average particle size of 4.2 μm and within ±8% in a mass ratio of 968:2:30. The test liquid in the container is delivered to a nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and a predetermined amount of the test liquid is vertically sprayed from the spray hole at the end of the nozzle to the acrylic plate, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm. In addition, the flow rates of the test liquid and the compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are as follows: the flow rate of the test liquid is greater than 100 ml / min and less than 150 ml / min, the flow rate of the compressed air is greater than 4.96 L / min and less than 7.44 L / min, the pressure of the compressed air is greater than 0.184 MPa and less than 0.277 MPa, and the pressure of the test liquid in the nozzle is greater than 0.169 MPa and less than 0.254 MPa.

[0283] After 4 g of the test liquid was sprayed, the spraying of the test liquid was temporarily stopped.

[0284] After the injection of the test liquid was temporarily stopped, the cross-sectional profile of the portion of the acrylic plate that collided with the spherical silica in the test liquid was measured.

[0285] Then, the erosion rate AcE (unit: "μm / g") of the acrylic plate was calculated by dividing the depth (μm) of the cross-sectional profile by the spraying amount (4 g) of the test liquid.

[0286] During the calibration, the erosion rate of the acrylic plate is set as a qualified condition within the range of ±5% based on 1.88 (μm / g), and the flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted so that the erosion rate of the acrylic plate is within the said range.

[0287] The phrase “the erosion rate is within a range of ±5% based on 1.88 (μm / g)” means, in other words, that the erosion rate is 1.786 (μm / g) or more and 1.974 (μm / g) or less.

[0288] <σ 0-20 / E 0-20 >

[0289] The plastic film is preferably such that a deviation in the erosion rate calculated from the erosion rate to a depth of 20 μm from the surface of the plastic film is defined as σ 0-20 When 0-20 / E 0-20 Less than 0.100.

[0290] In this specification, for σ 0-20 , can be calculated from the erosion rate of each cycle until the depth of the cross-sectional profile reaches 20 μm under the above-mentioned measurement conditions.

[0291] σ 0-20 / E 0-20 represents the coefficient of variation of the erosion rate, σ 0-20 / E 0-20 Small means that the erosion rate is unlikely to change in the thickness direction of the plastic film. 0-20 / E 0-20 When the value is 0.100 or less, the erosion rate in the thickness direction is stabilized and the pencil hardness can be easily improved.

[0292] σ 0-20 / E 0-20 The upper limit of is more preferably 0.080 or less, further preferably 0.070 or less, further preferably 0.060 or less, further preferably 0.055 or less.

[0293] σ 0-20 / E 0-20 The lower limit of is not particularly limited, but is usually greater than 0, preferably greater than 0.020, and more preferably greater than 0.035. 0-20 / E 0-20 When the value of is low, the plastic film may be weakly stretched. Plastic films with weak stretching tend to have poor solvent resistance, break easily, and have low stability against heat and humidity. 0-20 / E0-20 It is preferably 0.020 or more.

[0294] About σ 0-20 / E 0-20 Embodiments of the preferred numerical range of can include, for example, greater than 0 and less than 0.100, greater than 0 and less than 0.080, greater than 0 and less than 0.070, greater than 0 and less than 0.060, greater than 0 and less than 0.055, 0.020 or more and less than 0.100, 0.020 or more and less than 0.080, 0.020 or more and less than 0.070, 0.020 or more and less than 0.060, 0.020 or more and less than 0.055, 0.035 or more and less than 0.100, 0.035 or more and less than 0.080, 0.035 or more and less than 0.070, 0.035 or more and less than 0.060, 0.035 or more and less than 0.055.

[0295] The plastic film has two planes, the front side and the back side. The plastic film is preferably: 0-20 / E 0-20 and σ measured from the other side of the plane 0-20 / E 0-20 All are the above values.

[0296] The pencil hardness of the plastic film is preferably HB or higher, more preferably F or higher.

[0297] When the pencil hardness of the plastic film is too high, the in-plane phase difference of the plastic film tends to increase. Therefore, the pencil hardness of the plastic film is preferably 2H or less.

[0298] In this specification, pencil hardness is measured and determined according to the following procedures (1) to (6).

[0299] (1) A plastic film was cut into a sample having a size of 5 cm×10 cm to prepare.

[0300] (2) The plastic film is heated at 100° C. for 10 minutes. After heating, the plastic film is allowed to stand in an environment at 24° C. and a relative humidity of 40% to 60% for 30 to 60 minutes.

[0301] (3) For plastic films, pencil hardness was measured in accordance with the scratch hardness (pencil method) of JIS K 5600-5-4: 1999. Specifically, a pencil having a prescribed hardness was brought into contact with the surface of the plastic film at an angle of 45° and moved at a speed of 3.0 mm / sec under a load of 100 g to apply a load to the plastic film.

[0302] (4) After applying the load to the plastic film, the sample was heated again at 100° C. for 10 minutes.

[0303] (5) Immediately after re-warming, damage to the plastic film was visually evaluated. The visual evaluation was performed in an environment with a temperature of 24° C. and a relative humidity of 40% to 60%.

[0304] (6) The above-mentioned operations (1) to (5) are performed five times. The hardest pencil among the pencils that were not damaged in four or more of the five times is regarded as the pencil hardness of the plastic film to be evaluated.

[0305] In the above-mentioned pencil hardness measurement and determination method, when there is no damage in 4 out of 5 times with hardness B and there is no damage in 3 out of 5 times with hardness F, the hardness B is determined.

[0306] When the plastic film has a slow axis and a fast axis, the pencil hardness is preferably B or higher in both the slow axis direction and the fast axis direction. The slow axis of the plastic film refers to the direction in which the refractive index is the highest within the plane of the plastic film. The fast axis of the plastic film refers to the direction orthogonal to the slow axis within the plane of the plastic film.

[0307] The laminated structure of the plastic film may be a single-layer structure or a multi-layer structure, of which a single-layer structure is preferred.

[0308] In order to have good mechanical strength and suppress rainbow spots at the same time, the plastic film is preferably a biaxially stretched plastic film with a small in-plane phase difference. In addition, in order to reduce the in-plane phase difference of the stretched plastic film, it is preferred to make the stretching in the flow direction and the width direction nearly equal. In addition, in order to make the erosion rate of the plastic film within the above range, it is preferred to stretch the molecules uniformly within the surface of the plastic film. Therefore, in order to make the average in-plane phase difference and erosion rate of the plastic film within the above range, it is important to control the stretching. Regarding stretching control, in a multilayer structure, it is difficult to perform fine stretching control due to differences in the physical properties of each layer, but a single-layer structure is preferred in that it is easy to perform fine stretching control.

[0309] 《Example of manufacturing plastic film》

[0310] Hereinafter, examples of the production of plastic films will be described using a biaxially stretched plastic film as a representative example.

[0311] The biaxially stretched plastic film can be obtained by stretching a resin layer containing components constituting the plastic film. The stretching method includes sequential biaxial stretching and simultaneous biaxial stretching.

[0312] -Sequential biaxial stretching-

[0313] In the sequential biaxial stretching, after the cast film is stretched in the flow direction, stretching in the width direction of the film is performed.

[0314] The stretching in the flow direction is usually implemented by the peripheral speed difference of a pair of stretching rollers. The stretching in the flow direction can be carried out in one stage, or multiple stretching rollers can be used to carry out in multiple stages. In order to suppress the excessive deviation of optical characteristics such as in-plane phase difference, it is preferred to make multiple clamping rollers close to the stretching roller. The stretching ratio in the flow direction is usually more than 2 times and less than 15 times. In order to suppress the excessive deviation of optical characteristics such as in-plane phase difference, it is preferably more than 2 times and less than 7 times, more preferably more than 3 times and less than 5 times, and more preferably more than 3 times and less than 4 times.

[0315] In order to suppress excessive deviation of optical properties such as in-plane phase difference, the stretching temperature is preferably above the glass transition temperature of the resin and below the glass transition temperature + 100°C. In the case of PET, it is preferably above 70°C and below 120°C, more preferably above 80°C and below 110°C, and further preferably above 95°C and below 110°C. The stretching temperature refers to the set temperature of the device. In addition, even if the set temperature of the device is set within the range, it takes time for the temperature to stabilize. Therefore, it is preferred to set the temperature to the range and then manufacture the plastic film after the temperature stabilizes. In this specification, the set temperature of the device is described in multiple locations. The set temperatures of other locations are also the same as described above, and it is preferred to manufacture the plastic film after the temperature stabilizes.

[0316] Regarding the stretching temperature, by rapidly heating the film, the stretching interval at low temperature is shortened, thereby there is a tendency for the average value of the in-plane phase difference to become smaller. On the other hand, by slowly heating the film, the stretching interval at low temperature is extended, thereby there is a tendency for the orientation to be improved, the average value of the in-plane phase difference to be larger, and the deviation of the slow axis to be smaller.

[0317] When heating is performed during stretching, it is preferred to use a heater that generates turbulence. By heating with wind containing turbulence, a temperature difference is generated in a fine region within the film surface, and a fine deviation is generated on the orientation axis due to the temperature difference, so that condition A can be easily satisfied. By making the plastic film satisfy condition A, the Σ of the optical film can be easily T becomes the said range.

[0318] In the stretching in the flow direction, if the stretching time is shortened, the erosion rate tends to decrease, and if the stretching time is prolonged, the erosion rate tends to increase. The reason is believed to be that if the stretching time is short, it is difficult for the molecules in the surface of the plastic film to be stretched uniformly, while on the other hand, if the stretching time is long, it is easy for the molecules in the surface of the plastic film to be stretched uniformly. That is, in order to make E 0-20 Furthermore, by appropriately increasing the stretching ratio to a level that does not cause deviation in physical properties and extending the stretching time, E can be more easily made 0-20It is 1.4 μm / g or more.

[0319] The film stretched in the flow direction may be provided with functions such as slip, adhesion, antistatic properties, etc. by in-line coating or off-line coating. Before in-line coating or off-line coating, a surface treatment such as corona treatment, flame treatment, plasma treatment, etc. may be performed as needed.

[0320] In this specification, layers formed by in-line coating or off-line coating are not counted as the number of layers constituting the plastic film.

[0321] Regarding the stretching in the width direction, a tenter method is usually used, in which the two ends of the film are held by a clamp while being transported and stretched in the width direction. The stretching ratio in the width direction is usually more than 2 times and less than 15 times. In order to suppress excessive deviations of optical properties such as in-plane phase difference, it is preferably more than 2 times and less than 5 times, more preferably more than 3 times and less than 5 times, and further preferably more than 3 times and less than 4.5 times. It is preferred that the width stretching ratio is higher than the longitudinal stretching ratio.

[0322] The stretching temperature is preferably above the glass transition temperature of the resin and below the glass transition temperature + 110°C. In addition, it is preferred that the temperature be increased as it progresses from upstream to downstream. The stretching temperature refers to the set temperature of the device. The upstream side refers to the side close to the location where the stretching in the width direction is started. The downstream side refers to the side close to the location where the stretching in the width direction is ended. Specifically, when the transverse stretching interval is divided into two parts according to the length basis, the difference between the temperature of the upstream and the temperature of the downstream is preferably 20°C or more, more preferably 30°C or more, further preferably 35°C or more, and further preferably 40°C or more. In the case of PET, the stretching temperature of the first stage is preferably 80°C or more and 120°C or less, more preferably 90°C or more and 110°C or less, and further preferably 95°C or more and 105°C or less. By dividing the stretching interval in the width direction into two parts and setting a difference between the stretching temperatures of the first stage and the second stage, the surface temperature of the film during the stretching in the first stage and the surface temperature of the film during the stretching in the second stage can be controlled to different temperatures. Therefore, in each stretching step, orientation and oriented crystallization do not proceed excessively, and the plastic film can be prevented from becoming brittle, so that the pencil hardness can be easily increased.

[0323] In order to impart planarity and dimensional stability, the plastic film formed by sequential biaxial stretching as described above is preferably subjected to heat treatment in a tenter at a temperature above the stretching temperature and below the melting point. The heat treatment temperature refers to the set temperature of the device. Specifically, in the case of PET, it is preferably heat-fixed in the range of 140°C to 240°C, more preferably 200°C to 250°C. In order to suppress excessive deviations in optical properties such as in-plane phase difference, additional stretching of 1% to 10% is preferably performed in the first half of the heat treatment.

[0324] After the plastic film is heat treated, it is slowly cooled to room temperature and then wound up. As needed, relaxation treatment can also be used during heat treatment and slow cooling. In order to suppress excessive deviations in optical properties such as in-plane phase difference, the relaxation rate during heat treatment is preferably 0.5% or more and 5% or less, more preferably 0.5% or more and 3% or less, more preferably 0.8% or more and 2.5% or less, and more preferably 1% or more and 2% or less. In order to suppress excessive deviations in optical properties such as in-plane phase difference, the relaxation rate during slow cooling is preferably 0.5% or more and 3% or less, more preferably 0.5% or more and 2% or less, more preferably 0.5% or more and 1.5% or less, and more preferably 0.5% or more and 1.0% or less. In order to make the planarity good, the temperature during slow cooling is preferably 80°C or more and 140°C or less, more preferably 90°C or more and 130°C or less, more preferably 100°C or more and 130°C or less, and more preferably 100°C or more and 120°C or less. The temperature during the slow cooling is the set temperature of the device.

[0325] - Simultaneous biaxial stretching -

[0326] Simultaneous biaxial stretching is to introduce the cast film into a simultaneous biaxial tenter, hold both ends of the film with a clamp while conveying, and stretch it simultaneously and / or stepwise in the flow direction and the width direction. As a simultaneous biaxial stretching machine, there are a pantograph type, a screw type, a drive motor type, and a linear motor type, but preferably a drive motor type or a linear motor type that can arbitrarily change the stretch ratio and can perform relaxation treatment at any location.

[0327] The ratio of biaxial stretching is usually 6 times or more and 50 times or less in terms of area ratio. In order to suppress the excessive deviation of optical characteristics such as in-plane phase difference, the area ratio is preferably 8 times or more and 30 times or less, more preferably 9 times or more and 25 times or less, further preferably 9 times or more and 20 times or less, and further preferably 10 times or more and 15 times or less. In biaxial stretching at the same time, it is preferred that the stretching ratio in the flow direction and the stretching ratio in the width direction are in the range of 2 times or more and 15 times or less, so as to adjust the area ratio.

[0328] In the case of simultaneous biaxial stretching, in order to suppress the orientation difference in the plane, it is preferred that the stretching ratio in the flow direction and the width direction be substantially the same, and the stretching speed in the flow direction and the width direction be substantially the same.

[0329] In order to suppress excessive deviation of optical properties such as in-plane phase difference, the stretching temperature of the simultaneous biaxial stretching is preferably higher than the glass transition temperature of the resin and lower than the glass transition temperature + 120°C. In the case of PET, it is preferably higher than 80°C and lower than 160°C, more preferably higher than 90°C and lower than 150°C, and further preferably higher than 100°C and lower than 140°C. The stretching temperature refers to the set temperature of the device.

[0330] In order to impart planarity and dimensional stability, the film formed by simultaneous biaxial stretching is preferably further subjected to heat treatment above the stretching temperature and below the melting point in a heat fixing chamber in a tenter. The temperature of the heat treatment refers to the set temperature of the device. The conditions of the heat treatment are the same as those after the successive biaxial stretching.

[0331] <Low refractive index layer>

[0332] The low refractive index layer has the function of improving the anti-reflective property of the optical film and easily suppressing the rainbow spots when observed with the naked eye. The low refractive index layer is preferably located on the surface of the optical film on the side having the low refractive index layer based on the plastic film. In the range that does not hinder the effect of the optical film disclosed in the present invention, a functional layer such as an antifouling layer and an antistatic layer may also be provided on the low refractive index layer.

[0333] Light from the inside of the image display device toward the observer side is linearly polarized light when passing through the polarizer, but after passing through the plastic film, the polarization state of the linearly polarized light is disturbed, and it becomes light in which P waves and S waves exist. In addition, since there is a difference in reflectivity between the P wave and the S wave, and the reflectivity difference is wavelength-dependent, it is considered that rainbow spots can be seen with the naked eye. Here, in the case where a low refractive index layer is provided on the plastic film, the aforementioned reflectivity difference can be reduced, so it is considered that rainbow spots can be easily suppressed.

[0334] However, as described above, when the reflectivity of the optical film having the low refractive index layer is reduced, it is difficult to improve the uniformity of the color tone when observed from an oblique direction. This is believed to be caused by interference of reflected light from the optical film having the low refractive index layer.

[0335] Therefore, when the average refractive index of the low refractive index layer is defined as n1 and the average refractive index of the layer adjacent to the low refractive index layer is defined as n2, n2 / n1 is preferably less than 1.23. By making n2 / n1 less than 1.23, interference of reflected light can be suppressed, thereby making it easy to make the uniformity of color tone when observing from an oblique direction good.

[0336] n2 / n1 is more preferably less than 1.20, further preferably less than 1.15, and further preferably less than 1.13. In particular, by making n2 / n1 greater than 1.05 and less than 1.15, the wavelength dependence of the reflectivity can be easily suppressed. In addition, by making n2 / n1 greater than 1.05 and less than 1.15, the embrittlement of the low refractive index layer can be easily suppressed.

[0337] If n2 / n1 is too small, the visual reflectance Y value of the optical film tends to be high. Therefore, n2 / n1 is preferably 1.05 or more, and more preferably 1.07 or more.

[0338] The preferred range of n2 / n1 includes 1.05 or more and less than 1.23, 1.05 or more and 1.20 or less, 1.05 or more and 1.15 or less, 1.05 or more and 1.13 or less, 1.07 or more and less than 1.23, 1.07 or more and 1.20 or less, 1.07 or more and 1.15 or less, 1.07 or more and 1.13 or less, etc.

[0339] In order to easily adjust n2 / n1 to the above range, it is preferable to reduce the value of n2. Therefore, the layer adjacent to the low refractive index layer is preferably a plastic film or a hard coat layer, and more preferably a hard coat layer.

[0340] The average refractive index of each layer can be measured or calculated by the following method, for example, after confirming from a cross-sectional photograph of the laminate whether the thickness of each layer is more than 780 nm or less than 780 nm.

[0341] - Average refractive index of layers with a thickness exceeding 780 nm -

[0342] Regarding the average refractive index of a layer having a thickness exceeding 780 nm, the refractive index of the adhesive component of the layer is regarded as the refractive index of the layer. The average refractive index of a layer having a thickness exceeding 780 nm can be calculated, for example, by the following Baker method. The refractive index of a plastic film, a hard coat layer, and an anti-glare layer is preferably calculated by the Baker method.

[0343] Baker Act

[0344] This method is to shave off a layer to be measured for refractive index with a cutter or the like to prepare a sample in which the adhesive component is in a powdered state, and calculate by the Baker method in accordance with Method B (for powdered or granular transparent materials) of JIS K7142:2008.

[0345] - Average refractive index of layers with a thickness of 780 nm or less -

[0346] For the layer with a thickness of 780 nm or less, it is difficult to collect the adhesive component. Therefore, for the average refractive index of the layer with a thickness of 780 nm or less, for example, a laminate 1 with a layer with a thickness of 780 nm or less can be made, and calculated according to the following steps (Y1) and (Y2). The refractive index n1 of the low refractive index layer is preferably calculated according to the following steps (Y1) and (Y2).

[0347] (Y1) The average refractive index of the layer with a thickness exceeding 780 nm among the layers constituting the laminate 1 is calculated by the above-mentioned Beck method. Furthermore, the thickness of the layer with a thickness exceeding 780 nm and the thickness of the layer with a thickness of 780 nm or less are calculated from the cross-sectional photograph of the laminate.

[0348] (Y2) using the average refractive index and thickness information of the layer with a thickness exceeding 780nm calculated in (Y1), and the thickness information of the layer with a thickness below 780nm, and by the following fitting method, the average refractive index of the layer with a thickness below 780nm is calculated. The average refractive index n1 of the low refractive index layer is preferably in the range described below.

[0349] "Fitting Method"

[0350] This method is a method of calculating by fitting a reflection spectrum measured by a reflection photometer and a reflection spectrum calculated by an optical model of a multilayer thin film using Fresnel coefficients.

[0351] The average refractive index n2 of the layer adjacent to the low refractive index layer is preferably greater than the average refractive index n1 of the low refractive index layer. n2 is preferably in the following range: n1 is set to the range described later, and n2 / n1 satisfies the range. n2 is preferably 1.42 or more and 1.60 or less, and more preferably 1.45 or more and 1.58 or less.

[0352] From the viewpoint of suppressing rainbow spots, the refractive index of the low refractive index layer is preferably 1.45 or less, more preferably 1.43 or less, and even more preferably 1.40 or less.

[0353] If the refractive index of the low refractive index layer is too low, the optical film may have Σ T Therefore, the refractive index of the low refractive index layer is preferably 1.30 or more, more preferably 1.33 or more, and further preferably 1.35 or more.

[0354] The thickness of the low refractive index layer is preferably 60 nm or more and 200 nm or less, more preferably 80 nm or more and 120 nm or less, further preferably 85 nm or more and 110 nm or less, and further preferably 90 nm or more and 105 nm or less. The thickness of the low refractive index layer is preferably greater than the average particle size of the low refractive index particles such as hollow particles.

[0355] As a method for forming a low refractive index layer, it can be roughly divided into a wet method and a dry method. As a wet method, a method of forming by a sol-gel method using a metal alkoxide or the like, a method of forming by coating a low refractive index resin such as a fluororesin, and a method of forming by coating a low refractive index layer formed by containing low refractive index particles in a resin composition. As a dry method, a method of selecting particles with a desired refractive index from the low refractive index particles described later and forming by a physical vapor deposition method or a chemical vapor deposition method can be cited.

[0356] The wet method is superior to the dry method in terms of production efficiency, suppression of oblique reflection hue, and chemical resistance. In the wet method, for the purpose of adhesion, water resistance, scratch resistance, and low refractive index, it is preferably formed using a coating liquid for forming a low refractive index layer containing low refractive index particles in an adhesive resin composition.

[0357] As low refractive index particles, hollow particles and non-hollow particles can be cited. As low refractive index particles, only either hollow particles or non-hollow particles may be included, but preferably both hollow particles and non-hollow particles are included. By including both hollow particles and non-hollow particles, it is possible to suppress the reduction in coating strength and to easily and appropriately reduce the refractive index of the low refractive index layer. On the other hand, when only hollow particles are included, the refractive index of the low refractive index layer is excessively reduced, and the Σ of the optical film is reduced. T It is difficult to satisfy the range.

[0358] The material of the hollow particles and the non-hollow particles can be any inorganic compound or organic compound such as silica and magnesium fluoride, but silica is preferred to achieve a low refractive index and improve strength. The following description will focus on hollow silica particles and non-hollow silica particles.

[0359] Hollow silica particles refer to particles having an outer shell layer composed of silica, the interior of the particles surrounded by the outer shell layer is hollow, and air is contained in the hollow. Hollow silica particles are particles whose refractive index is reduced in proportion to the occupancy rate of gas compared with the original refractive index of silica by containing air. Non-hollow silica particles refer to particles that are not hollow inside like hollow silica particles. Non-hollow silica particles are, for example, solid silica particles.

[0360] The shapes of the hollow silica particles and non-hollow silica particles are not particularly limited, and may be substantially spherical shapes such as true spheres, rotational ellipsoids, and polyhedrons that can approximate spheres. Of these, true spheres, rotational ellipsoids, or substantially spherical shapes are preferred in consideration of scratch resistance.

[0361] Hollow silica particles contain air inside, so they play a role in reducing the refractive index of the entire low refractive index layer. By using hollow silica particles with a large particle size that has improved the air ratio, the refractive index of the low refractive index layer can be further reduced. On the other hand, there is a tendency of poor mechanical strength in hollow silica particles. Especially in the case of hollow silica particles with a large particle size that has improved the air ratio, there is a tendency to easily reduce the scratch resistance of the low refractive index layer.

[0362] The non-hollow silica particles play a role in improving the scratch resistance of the low refractive index layer by being dispersed in the binder resin.

[0363] In order to contain hollow silica particles and non-hollow silica particles at a high concentration in the adhesive resin and to uniformly disperse the particles in the resin in the film thickness direction, it is important to: bring the hollow silica particles close to each other; and, by setting the average particle size of the hollow silica particles and the average particle size of the non-hollow silica particles to a specified range, the non-hollow particles are allowed to enter between the hollow silica particles. The ratio of the average particle size of the non-hollow silica particles to the average particle size of the hollow silica particles (average particle size of the non-hollow silica particles / average particle size of the hollow silica particles) is preferably less than 0.29, more preferably less than 0.27. The ratio of the average particle size is preferably greater than 0.05, more preferably greater than 0.10.

[0364] The average particle size of the hollow silica particles is preferably smaller than the thickness of the low refractive index layer, and for example, 1 nm or more and 150 nm or less can be cited. The average particle size of the hollow silica particles is preferably 35 nm or more and 100 nm or less, more preferably 50 nm or more and 100 nm or less, and further preferably 60 nm or more and 80 nm or less.

[0365] The average particle size of the non-hollow silica particles is preferably smaller than the thickness of the low refractive index layer, and for example, 0.5 nm or more and 100 nm or less can be cited. The average particle size of the non-hollow silica particles is preferably 1 nm or more and 30 nm or less, more preferably 5 nm or more and 20 nm or less, and further preferably 10 nm or more and 15 nm or less.

[0366] The average particle size of the low refractive index particles can be calculated by the following operations (y1) to (y3).

[0367] (y1) Photographing a cross section of the low refractive index layer using STEM The acceleration voltage of STEM is preferably set to 10 kV or more and 30 kV or less, and the magnification is preferably set to 50,000 or more and 300,000 or less.

[0368] (y2) Ten random particles are extracted from the observed image, and the particle size of each particle is calculated. The particle size is measured as the distance between two random parallel straight lines in a combination of two straight lines that is the maximum distance between the two straight lines when the cross section of the particle is sandwiched. In the case of agglomerated particles, the agglomerated particles are measured as one particle.

[0369] (y3) The same operation is repeated five times for observation images of other screens of the same sample, and the value obtained by the number average of 50 particle diameters is taken as the average particle diameter of the low refractive index particles.

[0370] The hollow silica particles and non-hollow silica particles are preferably coated with a silane coupling agent on the surface. The silane coupling agent may be a general-purpose silane coupling agent, and a silane coupling agent having a (meth)acryloyl group or an epoxy group is preferred.

[0371] By subjecting the silica particles to a surface treatment using a silane coupling agent, the affinity between the silica particles and the binder resin is improved, and aggregation of the silica particles is less likely to occur. Therefore, the silica particles are easily dispersed uniformly.

[0372] The more the content of hollow silica particles, the higher the filling rate of hollow silica particles in the adhesive resin, and the lower the refractive index of the low refractive index layer. Therefore, relative to 100 parts by mass of the binding resin, the content of hollow silica particles is preferably 100 parts by mass or more, more preferably 120 parts by mass or more.

[0373] On the other hand, when the content of the hollow silica particles is too high, the hollow silica particles are easily damaged or fall off, and there is a tendency for the mechanical strength such as the scratch resistance of the low refractive index layer to decrease. When the content of the hollow silica particles is too high, there is a tendency for the refractive index of the low refractive index layer to decrease excessively, and the Σ T Therefore, the content of the hollow silica particles is preferably 200 parts by mass or less, more preferably 180 parts by mass or less, and further preferably 160 parts by mass or less relative to 100 parts by mass of the binder resin.

[0374] In order to improve the scratch resistance of the low refractive index layer, the content of the non-hollow silica particles is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, based on 100 parts by mass of the binder resin.

[0375] On the other hand, if the content of the non-hollow silica particles is too high, the non-hollow silica particles are easily aggregated. Therefore, the content of the non-hollow silica particles is preferably 100 parts by mass or less, more preferably 80 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0376] The binder resin of the low refractive index layer preferably includes a cured product of an ionizing radiation curable resin composition.

[0377] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter also referred to as an "ionizing radiation curable compound"). Examples of the ionizing radiation curable functional group include ethylenically unsaturated bonding groups such as (meth)acryloyl, vinyl, and allyl groups, as well as epoxy groups and oxetane groups.

[0378] As the ionizing radiation curable compound, a compound having an ethylenically unsaturated bond group is preferred, and a compound having two or more ethylenically unsaturated bond groups is more preferred, among which a polyfunctional (meth)acrylate compound having two or more ethylenically unsaturated bond groups is further preferred. As the polyfunctional (meth)acrylate compound, any monomer or oligomer can be used.

[0379] Ionizing radiation refers to electromagnetic waves or charged particle beams that have energy quanta that can cause molecules to polymerize or cross-link. Ultraviolet light (UV) or electron beams (EB) are usually used. In addition, electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion rays can also be used.

[0380] Examples of the bifunctional (meth)acrylate monomer in the polyfunctional (meth)acrylate compound include ethylene glycol di(meth)acrylate, bisphenol A tetraethoxy diacrylate, bisphenol A tetrapropoxy diacrylate, and 1,6-hexanediol diacrylate.

[0381] Examples of the trifunctional or higher-functional (meth)acrylate monomer include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate.

[0382] The (meth)acrylate monomers may be monomers in which a part of the molecular skeleton is modified, and monomers modified with ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc. may be used.

[0383] Examples of the polyfunctional (meth)acrylate oligomer include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate.

[0384] Urethane (meth)acrylate is obtained, for example, by reaction of a polyol and an organic diisocyanate with a hydroxy (meth)acrylate.

[0385] Preferred epoxy (meth)acrylates are: (meth)acrylates obtained by reacting trifunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with (meth)acrylic acid; (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with polybasic acids and (meth)acrylic acid; and (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with phenols and (meth)acrylic acid.

[0386] The ionizing radiation curable compound may be used alone or in combination of two or more.

[0387] When the ionizing radiation curable compound is an ultraviolet curable compound, the ionizing radiation curable resin composition preferably contains an additive such as a photopolymerization initiator or a photopolymerization accelerator.

[0388] Examples of the photopolymerization initiator include at least one selected from acetophenone, benzophenone, α-hydroxyalkylphenone, Michler's ketone, benzoin, benzyl dimethyl ketal, benzoylbenzoate, α-acyl oxime ester, α-aminoalkylphenone, anthraquinone, haloketone, and thioxanthones.

[0389] The photopolymerization accelerator can reduce polymerization hindrance caused by air during curing to accelerate the curing rate, and examples thereof include at least one selected from isopentyl p-dimethylaminobenzoate, ethyl p-dimethylaminobenzoate, and the like.

[0390] The low refractive index layer may contain a leveling agent for antifouling properties and surface smoothness. As for the leveling agent, fluorine-based and silicone-based are listed, but silicone-based is preferred. By containing a silicone-based leveling agent, the sliding property and antifouling property of the surface of the low reflectivity layer can be improved. As specific examples of "good antifouling property", examples of good fingerprint wiping properties and large contact angles with respect to pure water and hexadecane can be listed.

[0391] The content of the leveling agent is preferably 0.01 parts by mass or more and 10 parts by mass or less, and more preferably 0.05 parts by mass or more and 1 part by mass or less, relative to 100 parts by mass of the binder resin.

[0392] The low refractive index layer can be formed, for example, by applying a low refractive index layer-forming coating solution formed by dissolving or dispersing the components constituting the low refractive index layer and drying the coating solution. The low refractive index layer-forming coating solution may contain a solvent in order to adjust the viscosity or to dissolve or disperse the components.

[0393] <Reflectivity>

[0394] The optical film of the present disclosure has a visual reflectance Y value measured from the low refractive index layer side of preferably 4.0% or less, more preferably 2.0% or less, further preferably 1.7% or less, and further preferably 1.5% or less.

[0395] If the visual reflectivity of the optical film is too low, there is a Σ T Therefore, the visual reflectance Y value is preferably 0.5% or more, more preferably 0.7% or more, and even more preferably 1.0% or more.

[0396] In this specification, the visual reflectance Y value refers to the visual reflectance Y value of the CIE 1931 standard colorimetric system. The reflectance is preferably measured at 10 random locations of one sample and calculated as the average value of the 8 values ​​excluding the maximum and minimum values.

[0397] In this specification, the reflectivity of the optical film is measured as follows: a sample is prepared by bonding a black plate to the side of the optical film opposite to the reflectivity measurement surface via a transparent adhesive layer, and light is incident from the low refractive index layer side of the sample at an incident angle of 5° for measurement. The light source for measuring the reflectivity is preferably a C light source.

[0398] The difference in refractive index between the component (e.g., plastic film) in contact with the transparent adhesive layer of the sample and the transparent adhesive layer is preferably set within 0.15, more preferably within 0.10, more preferably within 0.05, and more preferably within 0.01. The black board is preferably a black board having a total light transmittance of 1% or less according to JIS K7361-1:1997, and more preferably 0%. The difference in refractive index between the resin constituting the black board and the transparent adhesive layer is preferably set within 0.15, more preferably within 0.10, more preferably within 0.05, and more preferably within 0.01.

[0399] <Haze, total light transmittance>

[0400] The haze of the optical film in accordance with JIS K7136:2000 is preferably 5% or less, more preferably 4% or less, and further preferably 3% or less. When anti-glare properties are required, the upper limit of the haze of the optical film may be 90% or less, 65% or less, or 40% or less. The haze of the optical film in accordance with JIS K7136:2000 is preferably 0.5% or more, more preferably 1.0% or more, and further preferably 1.5% or more. The haze refers to the haze of the entire optical film.

[0401] The total light transmittance of the optical film in accordance with JIS K7361-1:1997 is preferably 80% or more, more preferably 90% or more, further preferably 91% or more, and further preferably 92% or more.

[0402] <Other floors>

[0403] The optical film of the present disclosure may also have other layers other than the plastic film and the low refractive index layer. The low refractive index layer and other layers other than the low refractive index layer are preferably optically isotropic. The layer with optical isotropy refers to a layer with an in-plane phase difference of less than 20nm, preferably less than 10nm, and more preferably less than 5nm.

[0404] As other layers other than the plastic film and the low refractive index layer, antifouling layer, hard coating layer, antiglare layer and high refractive index layer etc. can be listed, and hard coating layer and antiglare layer are preferred. That is, the optical film of the present disclosure preferably has one or more layers selected from hard coating layer and antiglare layer between the plastic film and the low refractive index layer. Among them, hard coating layer is preferred. In the range that does not hinder the effect of the optical film of the present disclosure, the antifouling layer can be provided on the side of the low refractive index layer opposite to the plastic film. For example, in the range that does not hinder the effect of the optical film of the present disclosure, the plastic film, the low refractive index layer and the antifouling layer can be provided in sequence.

[0405] Hard coating

[0406] In order to improve the scratch resistance of the optical film, a hard coating is formed as required. The hard coating is preferably formed between the plastic film and the low refractive index layer. When the optical film further has a high refractive index layer, it is preferred to sequentially configure the hard coating, the high refractive index layer and the low refractive index layer on the plastic film.

[0407] In order to improve the scratch resistance, the hard coat layer preferably contains a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition, and more preferably contains a cured product of an ionizing radiation curable resin composition.

[0408] Thermosetting resin composition is a composition containing at least a thermosetting resin and is a resin composition that is cured by heating. Examples of thermosetting resins include acrylic resins, polyurethane resins, phenolic resins, urea-melamine resins, epoxy resins, unsaturated polyester resins, and silicone resins. In the thermosetting resin composition, a curing agent is added to these curable resins as needed.

[0409] The ionizing radiation curable resin composition of the hard coat layer may be the same as the ionizing radiation curable resin composition exemplified for the low refractive index layer.

[0410] In the ionizing radiation curable resin composition of the hard coat layer, a multifunctional (meth)acrylate oligomer is preferably included as an ionizing radiation curable compound. The lower limit of the number average molecular weight of the multifunctional (meth)acrylate oligomer is preferably 2000 or more, more preferably 2500 or more, and the upper limit is preferably 6000 or less, more preferably 5000 or less.

[0411] In the hard coating layer formed of a composition containing a multifunctional (meth)acrylate oligomer having a number average molecular weight of 2000 or more, the solvent of the coating liquid for forming the low refractive index layer or the ionizing radiation curable compound easily penetrates, so that reflection at the interface between the hard coating layer and the low refractive index layer can be suppressed. Therefore, interference of reflected light of the optical film can be easily suppressed, and Σ T Set to the range.

[0412] The hard coat layer formed of a composition containing a polyfunctional (meth)acrylate oligomer having a number average molecular weight of 6,000 or less can easily suppress a decrease in the hardness of the hard coat layer.

[0413] The content of the multifunctional (meth)acrylate oligomer having a number average molecular weight of 2000 to 6000 is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 12% by mass or more, relative to the total amount of ionizing radiation curable compounds in the ionizing radiation curable resin composition of the hard coat layer.

[0414] In order to achieve good scratch resistance, the thickness of the hard coating layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, further preferably 1.0 μm or more, and further preferably 2.0 μm or more. In order to suppress curling, the thickness of the hard coating layer is preferably 100 μm or less, more preferably 50 μm or less, more preferably 30 μm or less, more preferably 20 μm or less, more preferably 15 μm or less, and more preferably 10 μm or less.

[0415] Anti-glare layer

[0416] The anti-glare layer can be formed from, for example, an anti-glare layer-forming coating liquid containing a binder resin composition and particles. As the binder resin composition, for example, the curable resin composition exemplified in the hard coat layer can be used.

[0417] The particles may be either organic particles or inorganic particles. Examples of organic particles include particles made of polymethyl methacrylate, polyacrylic acid-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, silicone, fluorine resin, and polyester resin. Examples of inorganic particles include particles made of silicon dioxide, aluminum oxide, antimony, zirconium oxide, and titanium dioxide.

[0418] The average particle size of the organic particles in the antiglare layer cannot be generally determined because it varies depending on the thickness of the antiglare layer, but is preferably 0.5 μm to 10.0 μm, more preferably 1.0 μm to 8.0 μm, and further preferably 1.5 μm to 6.0 μm.

[0419] Inorganic particles are easily aggregated. Therefore, the average particle size of the inorganic particles is not limited to the above, but is preferably 1 nm or more and 10 μm or less.

[0420] The average particle size of the particles in the antiglare layer can be calculated by the following operations (z1) to (z3).

[0421] (z1) An image of the anti-glare layer is taken with an optical microscope or STEM. When the average particle size of the particles is micrometer level, it is preferred to use an optical microscope to take an image of the plane of the anti-glare layer. At this time, the magnification is preferably 500 times or more and 2000 times or less. When the average particle size of the particles is nanometer level, it is preferred to use STEM to take an image of the cross section of the anti-glare layer. At this time, the magnification is preferably 20000 times or more and 100000 times or less. The accelerating voltage of STEM is preferably 10kV or more and 30kV or less.

[0422] (z2) Extract 10 random particles from the observed image and calculate the particle size of each particle. The particle size is measured as the distance between two random parallel straight lines that sandwich the cross section of the particle and that maximize the distance between the two straight lines.

[0423] (z3) The same operation is repeated five times on another observed image of the same sample, and the value obtained by the number average of 50 particle diameters is taken as the average particle diameter of the particles in the antiglare layer.

[0424] The content of the particles in the anti-glare layer varies depending on the degree of the intended anti-glare property and therefore cannot be generalized, but is preferably from 1 part by mass to 100 parts by mass, more preferably from 5 parts by mass to 50 parts by mass, and further preferably from 10 parts by mass to 30 parts by mass, relative to 100 parts by mass of the resin component.

[0425] The anti-glare layer may contain fine particles having an average particle size of less than 500 nm in order to impart antistatic properties, control the refractive index, or adjust the shrinkage of the anti-glare layer caused by curing of the curable resin composition.

[0426] The thickness of the anti-glare layer is preferably 0.5 μm or more, more preferably 1.0 μm or more, and further preferably 2.0 μm or more. The thickness of the anti-glare layer is preferably 50 μm or less, more preferably 30 μm or more, more preferably 20 μm or less, more preferably 15 μm or less, and more preferably 10 μm or less. In order to make the hardness of the anti-glare layer good, the thickness of the anti-glare layer is preferably thicker than the average particle size of the particles.

[0427] <Example of layer structure>

[0428] The following (1) to (5) are examples of the layer structure of the optical film of the present disclosure. Among the following structures, (2) and (4) are preferred.

[0429] (1) A structure having a low refractive index layer on a plastic film.

[0430] (2) A structure having a hard coat layer and a low refractive index layer in this order on a plastic film.

[0431] (3) A structure having a high refractive index layer and a low refractive index layer in sequence on a plastic film.

[0432] (4) A structure having an anti-glare layer and a low refractive index layer in this order on a plastic film.

[0433] (5) A structure having a hard coat layer, a high refractive index layer, and a low refractive index layer in this order on a plastic film.

[0434] <Shape and size>

[0435] The optical film may be in the form of a single sheet cut into a specified size, or in the form of a roll in which a long strip is wound into a roll. The size of the single sheet is not particularly limited, but the maximum diameter is approximately 2 inches or more and 500 inches or less. In the present disclosure, the size of the single sheet is preferably 30 inches or more and 100 inches or less, and more preferably 40 inches or more and 100 inches or less. The "maximum diameter" refers to the maximum length when connecting any two points of the optical film. For example, when the optical film is rectangular, the diagonal of the rectangular area is the maximum diameter. When the optical film is circular, the diameter is the maximum diameter.

[0436] The width and length of the roll are not particularly limited. Generally speaking, the width is 500 mm to 5000 mm, and the length is about 100 m to 5000 m. The roll-shaped optical film can be cut into a single piece for use according to the size of the image display device, etc. When cutting, it is preferred to remove the end of the roll with unstable physical properties.

[0437] The shape of the single piece is not particularly limited, and can be, for example, a polygon (triangle, rectangle, pentagon, etc.), a circle, or a random amorphous shape. In the case of a rectangular optical film, the aspect ratio of the rectangle is not particularly limited as long as it does not cause problems as a display screen. For example, horizontal:vertical = 1:1, 4:3, 16:10, 16:9, 2:1, 5:4, etc. can be listed.

[0438] <Application>

[0439] The optical film of the present disclosure can be suitably used as an optical film for image display devices.

[0440] The optical film of the present disclosure can be suitably used as an optical film disposed on the light emitting surface side of a display element of an image display device. In this case, it is preferred that a polarizer is provided between the display element and the optical film of the present disclosure.

[0441] When the plastic film satisfies condition A, it is possible to suppress the crease from remaining or the breakage from occurring after the bending test regardless of the bending direction. Therefore, when the plastic film satisfies condition A, it can be more suitable for use as a plastic film for a curved image display device or a foldable image display device.

[0442] In addition, the optical film of the present disclosure can also be used as a component when manufacturing a functional film. For example, in a transfer sheet having a transfer layer on a substrate, the optical film of the present disclosure can be used as the substrate. In this case, it is sufficient to form a transfer layer on the side of the plastic film opposite to the side having the low refractive index layer. In addition, as the component, a substrate used to protect or enhance the functional film in the manufacturing process of the functional film can be listed.

[0443] [Polarizing plate]

[0444] The polarizing plate disclosed in the present invention comprises a polarizer, a first transparent protective plate located on one side of the polarizer, and a second transparent protective plate located on the other side of the polarizer, at least one of the first transparent protective plate and the second transparent protective plate is the above-mentioned optical film disclosed in the present invention, and the surface of the low refractive index layer side of the optical film faces the side opposite to the polarizer.

[0445] Figure 3 is a cross-sectional view showing an embodiment of a polarizing plate 700 of the present disclosure. Figure 3The polarizing plate 700 includes a polarizer 300, a first transparent protective plate 500 disposed on one side of the polarizer, and a second transparent protective plate 600 disposed on the other side of the polarizer. Figure 3 The polarizing plate 700 uses the optical film 100 as the first transparent protective plate 500. Figure 3 In the embodiment, the surface of the optical film 100 on the side of the low refractive index layer 30 faces the side opposite to the polarizer 300. Figure 3 In the polarizing plate 700 , the polarizer 300 , the first transparent protective plate 500 , and the second transparent protective plate 600 are stacked with the adhesive layer 400 interposed therebetween.

[0446] The polarizing plate is used, for example, to impart antireflection properties by combining it with a λ / 4 phase difference plate. In this case, the λ / 4 phase difference plate is disposed on the display element of the image display device, and the polarizing plate is disposed on the observer side of the λ / 4 phase difference plate.

[0447] When used in a liquid crystal display device, the polarizing plate is used to give the liquid crystal shutter function. In this case, in the liquid crystal display device, the lower polarizing plate, the liquid crystal display element, and the upper polarizing plate are arranged in this order from the backlight side, and the absorption axis of the polarizer of the lower polarizing plate is arranged orthogonal to the absorption axis of the polarizer of the upper polarizing plate. In the structure of the liquid crystal display device, the polarizing plate disclosed in the present invention can be used as the upper polarizing plate and the lower polarizing plate, and the polarizing plate disclosed in the present invention is preferably used as the upper polarizing plate. In the upper polarizing plate, as a transparent protective plate on the light emitting side of the polarizer, the optical film disclosed in the present invention is preferably used. In the lower polarizing plate, as a transparent protective plate on the light incident side of the polarizer, the optical film disclosed in the present invention is preferably used.

[0448] <Transparent protective plate>

[0449] The polarizing plate of the present disclosure uses the optical film of the present disclosure as at least one of the first transparent protective plate and the second transparent protective plate. Both the first transparent protective plate and the second transparent protective plate are preferably the optical film of the present disclosure.

[0450] When one of the first transparent protective plate and the second transparent protective plate is the above-mentioned optical film of the present disclosure, the other transparent protective plate is not particularly limited, but is preferably an optically isotropic transparent protective plate. In this specification, an optically isotropic transparent protective plate refers to a transparent protective plate having an in-plane phase difference of less than 20 nm, preferably less than 10 nm, and more preferably less than 5 nm. Examples of optically isotropic transparent protective plates include acrylic films, triacetyl cellulose films, polycarbonate films, amorphous olefin films, and the like.

[0451] <Polarizer>

[0452] Examples of polarizers include: sheet-type polarizers (polyvinyl alcohol films, polyvinyl formal films, polyvinyl acetal films, ethylene-vinyl acetate copolymer saponified films, etc.) formed by stretching films dyed with iodine or the like; wire grid polarizers composed of a plurality of metal wires arranged in parallel; coating polarizers coated with lyotropic liquid crystal and dichroic guest-host materials; and multilayer film polarizers, etc. These polarizers may be reflective polarizers that have the function of reflecting non-transmitted polarized light components.

[0453] The polarizer is preferably arranged so that the angle between its absorption axis and the slow axis of the plastic film is within 90 degrees ± 5 degrees, more preferably within 90 degrees ± 3 degrees, and even more preferably within 90 degrees ± 1 degree.

[0454] The image display device disclosed herein comprises a display element and a polarizer and an optical film arranged on the light emitting surface side of the display element, wherein the optical film is the optical film disclosed herein, and the surface of the optical film on the low refractive index layer side faces the side opposite to the display element.

[0455] Figure 4 is a cross-sectional view showing an embodiment of the image display device of the present disclosure.

[0456] Figure 4 The image display device 1000 has a light emitting surface side ( Figure 4 The optical film 100 is provided on the upper side of Figure 4 In the embodiment, the surface of the optical film 100 on the low refractive index layer side faces the side opposite to the display element 800 . Figure 4 The image display devices 100 of the embodiment of the present invention all include a polarizer 300 between the display element 800 and the optical film 100 .

[0457] The image display device 1000 is not limited to Figure 4 For example, in Figure 4 In the figure, the components constituting the image display device 1000 are arranged at predetermined intervals, but preferably, the components are integrally stacked via an adhesive layer or the like. The image display device may also have other components not shown, such as optical films. For example, the image display device may also have a surface plate such as a glass plate and a plastic plate. In the case where the image display device has a surface plate, the optical film disclosed in the present invention may be attached to the surface plate.

[0458] In the image display device of the present disclosure, the angle between the absorption axis of the polarizer and the slow axis of the plastic film of the optical film is preferably within 90 degrees ± 5 degrees, more preferably within 90 degrees ± 3 degrees, and even more preferably within 90 degrees ± 1 degree.

[0459] <Display components>

[0460] Display elements include liquid crystal display elements, EL display elements (organic EL display elements, inorganic EL display elements), plasma display elements, display elements using QD (Quantum dot), etc., and further LED display elements such as mini LED and micro LED display elements can be listed.

[0461] When the display element of the display device is a liquid crystal display element, a backlight is required on the surface of the liquid crystal display element on the opposite side to the resin sheet.

[0462] The image display device may be an image display device having a touch panel function.

[0463] Examples of the touch panel include a resistive film type, an electrostatic capacitance type, an electromagnetic induction type, an infrared type, and an ultrasonic type.

[0464] The touch panel function may be a case where the function is added to a display element like an in-cell touch panel liquid crystal display element, or a case where a touch panel is mounted on the display element.

[0465] If the plastic film satisfies condition A, it is possible to prevent the optical film from having creases or breaking after the bending test. Therefore, if the plastic film satisfies condition A, the image display device is preferably a curved image display device or a foldable image display device.

[0466] When the image display device is a curved image display device or a foldable image display device, the display element is preferably an organic EL display element. When the image display device is a curved image display device or a foldable image display device, the glass contained in the image display device is preferably thin glass. The thickness of the thin glass is preferably 5 μm or more and 80 μm or less.

[0467] <Other plastic films>

[0468] The image display device of the present disclosure may have other plastic films within a range not impairing the effects of the present disclosure.

[0469] As the other plastic film, a plastic film having optical isotropy is preferred.

[0470] [Method for selecting optical film for image display device]

[0471] The method for selecting an optical film for an image display device disclosed herein is a method for selecting an optical film for an image display device having a polarizer and an optical film on a light emitting surface of a display element, wherein an optical film X satisfying the following determination conditions (1) to (4) is selected as the optical film.

[0472] (1) is an optical film X having a low refractive index layer on a plastic film;

[0473] (2) The plastic film has: a slow axis which is an axis with the highest refractive index in the plane; and a fast axis which is an axis orthogonal to the slow axis in the plane of the plastic film;

[0474] (3) The low refractive index layer is located on the surface of the optical film X; and

[0475] (4) The optical film X has a Σ calculated under the following measurement condition 1. T The area that is greater than 0.04 and less than 0.20.

[0476] <Measurement Condition 1>

[0477] Linearly polarized light is incident from the surface of the optical film opposite to the low refractive index layer. The incident linearly polarized light is defined as light L1. Transmitted light after the light L1 passes through the optical film is defined as light L2.

[0478] The light L1 is incident on the optical film at an angle of 50 to 70 degrees with the elevation angle of the vibration direction of the light L1 being fixed at 45 degrees with the slow axis being fixed at 45 degrees. The light L2 is measured at 11 elevation angles by varying the elevation angle by 2 degrees within the range of 50 to 70 degrees. The light L2 is measured at 11 measurement points through the above measurement.

[0479] The light L2 is converted to the conditions of C light source and viewing angle of 2 degrees. For the light L2 at the nth measurement point among the 11 measurement points, the a* value and b* value of the L*a*b* colorimetric system are defined as a*n and b*n. In addition, for the light L2 at the n+1th measurement point among the 11 measurement points, the a* value and b* value of the L*a*b* colorimetric system are defined as a*n1 and b*n1.

[0480] Based on the measurements of the 11 measurement points, the sum of the square of the difference between the a* of the adjacent measurement points and the square of the difference between the b* of the adjacent measurement points is calculated. The sum is calculated at each of the 10 adjacent points, and ∑ T The Σ T It can be represented by the following formula 1.

[0481] ∑ T =∑[{a*na*n1} 2 +{b*nb*n1} 2 ] (Formula 1)

[0482] In the method for selecting an optical film for an image display device disclosed herein, the angle between the absorption axis of the polarizer and the slow axis of the plastic film of the optical film is preferably within 90 degrees ± 5 degrees, more preferably within 90 degrees ± 3 degrees, and even more preferably within 90 degrees ± 1 degree.

[0483] The embodiment of the measurement condition 1 in the method of selecting an optical film for an image display device of the present disclosure is the same as the embodiment of the measurement condition 1 of the optical film of the present disclosure described above.

[0484] In the method for selecting an optical film for an image display device disclosed in the present invention, it is preferred to further include additional determination conditions as determination conditions. As additional determination conditions, preferred embodiments of the optical film disclosed in the present invention (e.g., Formula 2-1, Formula 2-2, n2 / n1, in-plane phase difference of a plastic film, etc.) can be listed.

[0485] The method for selecting an optical film for an image display device disclosed in the present invention is useful as a method for selecting an optical film for an image display device having a polarizer on a surface on the light emitting surface side of a display element.

[0486] Example

[0487] Next, the present disclosure will be described in more detail by way of examples, but the present disclosure is not limited to these examples.

[0488] 1. Measurement and evaluation

[0489] The following measurement and evaluation atmosphere is: temperature 23 ° C ± 5 ° C, relative humidity 40% or more and 65% or less. In addition, before the measurement and evaluation, the sample for measurement is exposed to the atmosphere for 30 minutes or more and 60 minutes or less. The sample for measurement is collected from a clean and undamaged part. The measurement and evaluation are carried out in a state where the planarity of the sample is good.

[0490] 1-1. Measurement under measurement condition 1

[0491] A 5 cm x 5 cm sample was cut from the optical film of the experimental example. The sample was measured under measurement condition 1. The measurement device used was a spectrophotometer of JASCO Corporation, product number "V-7100". Based on the measurement results, the "Σ of Formula 1" was calculated. T ”, “(a*max-a*min) of Formula 2-1”, “(b*max-b*min) of Formula 2-2”, “the maximum value of the sum (S MAX ). Under measurement condition 1, the sum of the square of the difference between the a* of the adjacent measurement points and the square of the difference between the b* of the adjacent measurement points is calculated at 10 adjacent points. The maximum value of the sum (S MAX)” refers to the maximum value of the sum at 10. In addition, the visual reflectance Y value of the optical film of the experimental example is defined as “R (%)”, and “R×Σ T " (The visual reflectance Y value was measured by the method 1-6 described later). The results are shown in Table 1.

[0492] 1-2.n1 and n2

[0493] Regarding the optical film of the experimental example, the average refractive index n1 of the low refractive index layer was measured by using the Baker method and the fitting method described in the main text of the specification in combination.

[0494] In addition, regarding the optical film of the experimental example, the average refractive index n2 of the layer adjacent to the low refractive index layer was measured. In the case where the layer adjacent to the low refractive index layer is any of a plastic film and a hard coat layer, n2 was also measured using the Baker method described in the main text of the specification. The results are shown in Table 1.

[0495] 1-3. Rainbow light spots

[0496] A liquid crystal display device having a polarizer on a liquid crystal display element (trade name "EV2450" of EIZO Corporation; horizontal: 527.0 mm, vertical: 596.4 mm; absorption axis of the polarizer parallel to the vertical direction of the screen; backlight: backlight using white light emitting diodes) was prepared.

[0497] A laminated body was prepared by laminating the optical film of the experimental example on the liquid crystal display device via an adhesive layer. At this time, the absorption axis of the polarizer was arranged at 90 degrees to the slow axis of the plastic film of the optical film. Then, the laminated body was displayed in white in a darkroom environment, and observed from all positions and all directions at a distance of more than 30 cm and less than 100 cm from the laminated body. The evaluators were healthy people aged 20 to 40 with a visual acuity of more than 0.7, and the presence or absence of rainbow spots was evaluated with the naked eye according to the following criteria. The visual acuity also includes corrected visual acuity. The results are shown in Table 1.

[0498] AA: Rainbow flares are not observable when viewed from all positions and in all directions.

[0499] A: The rainbow spots exist slightly in the position where they are observed in a very small area, or the rainbow spots exist slightly in the direction where they are observed in a very small area.

[0500] B: The rainbow spots exist in large numbers at locations where they are observed in a very small area, or the rainbow spots exist in large numbers in directions where they are observed in a very small area.

[0501] B -: Rainbow spots exist in large numbers at positions where they are observed in a part of the region, or rainbow spots exist in large numbers in directions where they are observed in a part of the region.

[0502] C: The rainbow spots exist in large numbers at positions where they are observed in most areas, or the rainbow spots exist in large numbers in directions where they are observed in most areas.

[0503] 1-4. Uniformity of color tone

[0504] With the power off, visually observe the laminate produced in 1-3 in a bright room environment. The conditions of the bright room are: the brightness of the surface of the laminate is in the range of 1000 lux or more and 1500 lux or less. Observe from three directions: the front direction of the laminate, the direction of about 50 degrees relative to the laminate, and the direction of about 70 degrees relative to the laminate. The distance between the laminate and the eyes of the evaluator is more than 30 cm and less than 100 cm. The evaluators are 20 healthy people aged 20 to 40 with a visual acuity of more than 0.7, and the uniformity of the color tone when observed obliquely is evaluated according to the following criteria. The results are shown in Table 1.

[0505] A: When comparing the color tones in the three directions, more than 18 people answered that they could not feel the change in color tones.

[0506] B: When comparing the color tones in the three directions, 15 or more and 17 or less people answered that they could not feel the change in color tones.

[0507] C: When comparing the color tones in the three directions, 10 or more and 14 or less people answered that they could not feel the change in color tones.

[0508] D: When comparing the color tones in the three directions, 5 or more and 9 or less people answered that they could not feel the change in color tones.

[0509] E: When comparing the color tones in the three directions, less than 4 people answered that they could not feel the change in color tones.

[0510] 1-5. Chroma based on reflected light

[0511] A sample (5 cm×5 cm) was prepared by bonding a black plate (KURARAY CO., LTD.; product name: COMOGLAS DFA2CG 502K (Black) type; total light transmittance: 0%; thickness: 2 mm; refractive index: 1.49) to the plastic film side of the optical film of the experimental example via a transparent adhesive layer with a thickness of 25 μm (PANAC CO., LTD.; product name: "Panaclean PD-S1"; refractive index: 1.49).

[0512] When the direction perpendicular to the surface of the low refractive index layer side of the sample is set to 0 degrees, light is incident on the sample from the directions of 5 degrees, 50 degrees, and 70 degrees, and the chroma is measured based on the regular reflected light of the incident light. The chroma at 10 locations is measured for each sample, and the average value is used as the chroma at each angle of each sample. Chroma (C*) can be calculated based on the a* value and b* value of the L*a*b* color system and by the following formula.

[0513] C*={(a*) 2 +(b*) 2} 1 / 2

[0514] The measuring device used was a spectrophotometer product numbered "V-7100" from JASCO Corporation. The measuring device measured within a wavelength range of 380 nm to 780 nm, and then the brightness felt by the human eye was converted using software [software built into the measuring device <JASCO Corporation product numbered "JASCO Spectrum Manager">. Conditions for calculating reflectivity: C light source and 2 degree viewing angle] to perform conversion. The results are shown in Table 1.

[0515] For optical films having no low refractive index layer, the chromaticity was not measured.

[0516] 1-6. Visual reflectivity Y value (reflectivity)

[0517] When the direction perpendicular to the surface of the low refractive index layer side of the sample prepared in 1-5 was defined as 0 degrees, light was incident on the sample from a direction of 5 degrees, and the reflectance (visual reflectance Y value) was measured based on regular reflection light of the incident light.

[0518] The measuring device used is a spectrophotometer product numbered "V-7100" from JASCO Corporation. The measuring device performs measurements within a wavelength range of 380 nm to 780 nm, and then uses software for converting to brightness perceived by the human eye [software built into the measuring device <JASCO Corporation product numbered "JASCO Spectrum Manager">. Conditions for calculating reflectivity: C light source and 2 degree viewing angle] to perform conversion. The reflectivity of each sample was measured at 10 locations, and the average value was taken as the visual reflectivity Y value of each sample. The results are shown in Table 1.

[0519] For optical films without a low refractive index layer, the visual reflectance Y value was not measured.

[0520] 1-7. In-plane phase difference (Re), phase difference in thickness direction (Rth), and direction of slow axis

[0521] A sample of 50 mm in length and 50 mm in width is cut out from the plastic film produced or prepared by "2" described later and used in the experimental examples and reference examples. At this time, the flow direction (MD direction) of the plastic film is regarded as the longitudinal direction, and the width direction (TD direction) of the plastic film is regarded as the transverse direction. The in-plane phase difference, the phase difference in the thickness direction, and the direction of the slow axis are measured for the four locations of the location 10 mm forward from the four corners of the sample toward the center, and the total of five locations in the center of the sample. The average value of Re1 to Re5, etc. is calculated from the measurement results. The results are shown in Table 2.

[0522] The measuring device used was a product named "RETS-100 (measuring point: 5 mm diameter)" manufactured by Otsuka Electronics Co., Ltd. The slow axis direction was measured in the range of 0 degrees to 90 degrees, with the flow direction (MD direction) of the plastic film as 0 degrees as the reference.

[0523] 1-8.Bending resistance

[0524]

[0525] A long strip sample of 30 mm in width direction (TD direction) × 100 mm in flow direction (MD direction) was cut out from the plastic film produced or prepared by "2" described later and used in the experimental examples and reference examples. The two ends of the short side (30 mm side) of the sample were fixed to a durability testing machine (product name "DLDMLH-FS", Yuasa System Co., Ltd.), and then a continuous folding test of 100,000 folds of 180 degrees was performed. An area 10 mm away from the end of the sample was fixed at both ends of the short side of the sample. The folding speed was 120 times per minute. A more detailed method of the folding test is shown below.

[0526] After the folding test, the long strip sample is placed on a horizontal table and the angle at which the end of the sample is lifted from the table is measured. If the angle is less than 15 degrees, it is a qualified level. The case where the sample breaks in the middle is defined as "break". The results are shown in Table 2. Through this evaluation, the bending resistance in the TD direction (≈slow axis direction) can be evaluated.

[0527] <MD direction>

[0528] From the biaxially stretched plastic film produced or prepared by "2" described later and used in the examples and comparative examples, a strip sample of 30 mm in the flow direction (MD direction) and 100 mm in the width direction (TD direction) was cut out and the same evaluation as above was performed. This evaluation can evaluate the bending resistance in the MD direction (≈fast axis direction).

[0529] <Details of folding test>

[0530] like Figure 6 As shown in (A) of FIG. 1 , in the continuous folding test, first, the side portion 10C of the plastic film 10 and the side portion 10D facing the side portion 10C are fixed by the fixing portions 60 arranged in parallel. The fixing portions 60 can slide in the horizontal direction.

[0531] Then, if Figure 6 As shown in (B), by moving the fixing parts 60 closer to each other, the plastic film 10 is deformed in a folded manner. Figure 6 As shown in (C), after the fixing part 60 is moved to a position where the interval between two opposing sides of the plastic film 10 fixed by the fixing part 60 becomes 10 mm, the fixing part 60 is moved in the reverse direction, thereby eliminating the deformation of the plastic film 10.

[0532] like Figure 6As shown in (A) to (C), the plastic film 10 can be folded 180 degrees by moving the fixing portion 60. In addition, the continuous folding test is performed in a manner that the curved portion 10E of the plastic film 10 does not protrude from the lower end of the fixing portion 60, and the interval when the fixing portion 60 is closest is controlled to 10 mm, thereby making it possible to make the interval between the two opposing sides of the optical film 10 10 mm.

[0533] 1-9. Pencil hardness

[0534] The pencil hardness of the polyester films 1-5 of "2" below was measured. The pencil hardness was measured in accordance with the steps (1) to (6) of the main text of the specification. For commercially available polyester films having an easy-adhesive layer formed on one side in advance, the pencil hardness of the surface without the easy-adhesive layer was measured. The pencil hardness was measured on both the slow axis and the fast axis. The results are shown in Table 2.

[0535] 1-10. Erosion rate

[0536] The erosion rate of the following polyester films 1 to 5 of "2" was measured using an erosion rate measuring device (MSE test device from Palmeso Co., Ltd., product number "MSE-A203", the cross-sectional shape of the nozzle was a 1 mm x 1 mm square, and the cross-sectional profile was measured by a stylus method), and E was calculated. 0-20 The measurement area of ​​erosion rate is 1mm×1mm.

[0537] The erosion rate of each sample was measured after the following calibration was performed using a standard acrylic plate. In addition, the test liquid was prepared before calibration, and a dispersion operation was performed in advance before calibration. In addition, regarding the standard acrylic plate, AcE (the average value of the erosion rate of the acrylic plate measured under measurement condition A) in the main text of the specification was within the range of 1.786 μm / g or more and 1.974 μm / g or less.

[0538] (0-1) Preparation of test solution

[0539] In a beaker, prepare the following test solution and mix it with a glass rod: the test solution is a mixture of pure water, a dispersant (a product called "Demol N" by Wako Pure Chemical Industries), and spherical silica with an average particle size (median particle size) of 3.94 μm (model "MSE-BS-5-3" designated by Palmeso Co., Ltd., full width at half maximum of particle size distribution: 4.2 μm) in a mass ratio of 968:2:30. After placing the adjusted test solution and a stirring element in a container (tank), cover the tank and install a fixture. Next, place the tank in a measuring device. In the present embodiment, as the model "MSE-BS-5-3" designated by Palmeso Co., Ltd., a product number "BS5-3" of Potters-Ballotini Co., Ltd. is used.

[0540] (0-2) Distributed operation

[0541] After placing the tank containing the test liquid in the measuring device, set the dummy sample on the sample mounting table. Next, press the buttons "Erosion force setting" and "Go" on the operation panel of the measuring device body in sequence. Next, input the specified values ​​as the flow rate of the test liquid and compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle, and project the test liquid onto the dummy sample. After stopping the projection, press the buttons "Return", "Finish", and "Confirm" on the operation panel in sequence.

[0542] (1) Calibration

[0543] An acrylic plate with a thickness of 4 mm as a calibration sample was fixed to the sample mounting table of the measuring device by double-sided tape ("Kapton double-stick tape" produced by Nitto Denko America, product number: P-223 1-6299-01). The acrylic plate was a PMMA plate.

[0544] Next, the sample mounting table to which the acrylic plate was fixed was placed on the measuring device.

[0545] Next, unlock the micrometer and use the altimeter to adjust the height of the sample mounting table. Adjust the distance between the injection hole of the measuring device and the acrylic plate to 4 mm.

[0546] Next, the button "Processing condition input screen" on the operation panel of the measuring device body was pressed, and the setting was "Number of Steps: 1; Specify the injection amount g x 1 time". The injection amount was 4 g.

[0547] Next, press the buttons "Setting Complete", "Start Operation", and "Yes" on the operation panel in sequence. The flow rates of the test liquid and compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are maintained at the values ​​entered in "(0-2) Dispersion Operation".

[0548] Next, click "Online" on the operation screen of the data processing PC to cancel the online state and change to offline state.

[0549] Next, "Descent" is clicked on the operation screen to lower the stylus of the stylus-type step gauge of the cross-sectional profile acquisition unit.

[0550] Next, confirm that the lock of the micrometer is released and turn the micrometer upward. At this time, adjust it so that the red arrow on the monitor comes to the center. Through the adjustment, the stylus of the stylus step gauge contacts the surface of the calibration sample, and the 0 point of the z-axis as the height direction can be adjusted.

[0551] Next, the lock of the micrometer is switched from released (off) to on.

[0552] Next, click "Raise" to raise the stylus of the stylus-type step gauge of the cross-sectional profile acquisition unit.

[0553] Next, click "offline" on the operation screen of the data processing PC to cancel the offline state and switch to online state.

[0554] Next, the cover of the measuring device body was closed, and the button "Confirm" on the operation panel of the measuring device body was pressed to spray 4 g of the test liquid.

[0555] After stopping the injection of the test liquid, click "Go" to calculate the erosion rate. If the erosion rate is within the range of ±5% based on 1.88 (μm / g), the calibration is completed. If the erosion rate deviates from the above range, adjust the flow rate of the test liquid, the flow rate of the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle, and repeat the calibration until the erosion rate is within the above range.

[0556] (2) Measurement of the erosion rate of each sample

[0557] (2-1) Sample installation

[0558] A laminated body was prepared by laminating a sample (polyester films 1 to 5 of "2" below) to a stainless steel plate, and the laminated body was fixed to a sample mounting table with a double-sided tape ("Kapton double-stick tape" from Nitto Denko America; product number: P-223 1-6299-01). The sample had a size of 1 cm x 1 cm.

[0559] Next, place the sample mounting table on the measuring device. Then, unlock the micrometer and use the altimeter to adjust the height of the sample mounting table. Adjust the distance between the injection hole of the measuring device and the plastic film to 4 mm.

[0560] Next, after pressing the button "Processing Condition Input Screen" on the operation panel of the measuring device body, enter the number of steps and the injection amount of the test liquid (g / time) for each step. The injection amount for each step is set to a range of 0.5 g or more and 3.0 g or less. The flow rates of the test liquid and compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are maintained to the conditions that passed the "(1) Calibration".

[0561] Next, press the buttons "Setting Complete", "Start Operation", and "Yes" on the operation panel in sequence.

[0562] Next, click "Online" on the operation screen of the data processing PC to cancel the online state and change to offline state.

[0563] Next, "Descent" is clicked on the operation screen to lower the stylus of the stylus-type step gauge of the cross-sectional profile acquisition unit.

[0564] Next, confirm that the lock of the micrometer is released and turn the micrometer upward. At this time, adjust it so that the red arrow on the monitor comes to the center. Through the adjustment, the stylus of the stylus step gauge contacts the surface of the calibration sample, and the 0 point of the z-axis as the height direction can be adjusted.

[0565] Next, the lock of the micrometer is switched from released (off) to on.

[0566] Next, click "Raise" to raise the stylus of the stylus-type step gauge of the cross-sectional profile acquisition unit.

[0567] Next, click "offline" on the operation screen of the data processing PC to cancel the offline state and switch to online state.

[0568] (2-2) Measurement starts

[0569] Close the cover of the measuring device body, press the button "Confirm" on the operation panel of the measuring device body, and perform the measurement with the injection of the test liquid and the measurement of the cross-sectional profile as one cycle until the depth of the cross-sectional profile exceeds 20 μm. Specifically, perform the measurement until the depth of the cross-sectional profile is 25 μm or more and 30 μm or less.

[0570] After measurement, start the attached software "MseCalc" and click "Analysis Method". Next, click "Average Analysis". Next, click "Add" twice in the average analysis screen, and "A-1" and "A-2" will be displayed in the analysis name column. Double-click the "Baseline" column of "A-1" and "0" will be displayed in the Baseline column.

[0571] Next, click "A-1" on the average value analysis screen to activate it, and operate the position of the X-axis position bar. The position of the position bar is determined as the part of the plastic film that is not worn in the cross-sectional profile screen.

[0572] Next, click A-2 on the average value analysis screen to activate it, and operate the position of the X-axis position bar. The position of the position bar is determined as the deepest part of the plastic film worn in the cross-sectional profile screen.

[0573] Next, the cross-sectional profile and erosion rate data of each step are exported to csv format, and the erosion rate E is calculated. 0-20 Specifically, the “Erosion Rate (corrected)” with a depth of 0 μm or more and 20 μm or less in the csv output data is averaged to calculate the erosion rate E. 0-20 The results are shown in Table 2.

[0574] 2. Production and preparation of plastic film

[0575] [Polyester film 1]

[0576] 1 kg of PET (melting point: 258°C, absorption center wavelength: 320 nm) and 0.1 kg of ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinone-4-one) were melt-mixed at 280°C in a kneader to prepare pellets containing the ultraviolet absorber. The pellets and PET having a melting point of 258°C were put into a single screw extruder, melt-mixed at 280°C, and then extruded from a T-die, thereby casting on a casting drum whose surface temperature was controlled at 25°C to obtain a cast film. The amount of the ultraviolet absorber in the cast film was 1 part by mass relative to 100 parts by mass of PET.

[0577] The obtained cast film was heated with a roller set at 95°C, and then the film temperature at a point of 250 mm in the 400 mm stretching section was 103°C. The film was stretched 3.3 times in the flow direction while being heated by a radiation heater on both sides of the film, and then temporarily cooled to obtain a uniaxially stretched film. The starting point of the stretching section was the stretching roller A, and the end point was the stretching roller B, and the stretching rollers A and B each had two pressure rollers. When heating with a radiation heater, a wind of 92°C and 4m / s was blown toward the film from the side of the radiation heater opposite to the film, thereby generating turbulence on the front and back sides of the film, thereby disturbing the temperature uniformity of the film.

[0578] Next, the wetting tension of the base film was adjusted to 55 mN / m by subjecting both surfaces of the uniaxially stretched film to corona discharge treatment in air. Next, a "slippery layer coating liquid containing a polyester resin having a glass transition temperature of 18°C, a polyester resin having a glass transition temperature of 82°C, and silica particles having an average particle size of 100 nm" was applied online to the corona discharge treated surfaces of both surfaces of the film to form a slippery layer.

[0579] Next, the uniaxially stretched film is introduced into a tenter, and after being preheated with hot air at 95°C, it is stretched 4.5 times in the width direction of the film at a temperature of 105°C in the first stage and 140°C in the second stage. Here, when the stretching interval in the width direction is divided into two parts, the stretching is performed in two stages in such a way that the stretching amount of the film at the middle point of the stretching interval in the width direction becomes 80% of the stretching amount at the end of the stretching interval in the width direction. The aforementioned "stretching amount" refers to the difference between the film width at the measuring point and the film width before stretching. The film stretched in the width direction is directly heat-treated with hot air in the tenter. The temperature of the hot air rises from 180°C to 245°C in stages. Next, a 1% relaxation treatment is performed in the width direction under the same temperature conditions, and then it is rapidly cooled to 100°C, and then a 1% relaxation treatment is performed in the width direction. Then, it is rolled up to obtain a biaxially stretched polyester film 1 with a thickness of 40μm.

[0580] Polyester film 1 was used as the plastic film of Experimental Example 3.

[0581] [Polyester film 2]

[0582] A biaxially stretched polyester film 2 having a thickness of 40 μm was obtained in the same manner as the biaxially stretched polyester film 1 except that the stretching ratio in the width direction was changed from 4.5 times to 5.1 times.

[0583] [Polyester film 3]

[0584] As the polyester film 3 , a commercially available biaxially stretched polyester film (TOYOBO CO., LTD.; trade name: Cosmoshine A4300; thickness: 38 μm) was prepared. The polyester film 3 was used as the plastic film of Experimental Example 1.

[0585] [Polyester film 4]

[0586] As the polyester film 4 , a commercially available biaxially stretched polyester film (TOYOBO CO., LTD.; trade name: Cosmoshine A4100; thickness: 50 μm) was prepared. The polyester film 4 was used as the plastic film of Reference Example 1.

[0587] [Polyester film 5]

[0588] As the polyester film 5 , a commercially available uniaxially stretched polyester film (TOYOBO CO., LTD.; trade name: Cosmoshine TA044; thickness: 80 μm) was prepared. The polyester film 5 was used as the plastic film of Reference Example 2.

[0589] 3. Synthesis of compounds

[0590] The compound α used in “4. Preparation of coating liquid” was synthesized by the following method.

[0591] Air gas is introduced into a reaction vessel equipped with a stirrer, a thermometer, a cooling tube and a nitrogen inlet tube. The pressure of the reaction vessel when the air gas is introduced is controlled to 1.0 atmosphere ± 0.1 atmosphere. Then, 57 parts by mass of pentaerythritol triacrylate, 43 parts by mass of pentaerythritol tetraacrylate, 0.02 parts by mass of dibutyltin dilaurate, 0.02 parts by mass of p-methoxyphenol, and 30 parts by mass of butyl acetate are added to the reaction vessel, and the temperature is raised to 60°C while stirring under a nitrogen stream. The pressure of the reaction vessel under a nitrogen stream is controlled to 1.2 atmospheres ± 0.1 atmospheres. (By making the pressure under a nitrogen stream higher than normal pressure, the oxygen concentration in the reaction vessel can be more effectively reduced.) Then, 30 parts by mass of hexamethylene diisocyanate are added to the dropping container, and it is evenly dropped into the reaction container in 1 hour. After the dropwise addition, the temperature of the reaction container is raised to 75°C and kept warm at 75±3°C for 6 hours. Then, 150 parts by mass of methyl ethyl ketone was added to obtain a transparent resin solution. Finally, the solvent was removed using an evaporator to obtain compound α. Compound α is an ionizing radiation curable compound. The number average molecular weight of compound α is about 4500.

[0592] 4. Preparation of coating solution

[0593] A coating liquid used in "5. Preparation of optical film" was prepared.

[0594] <Hard coat layer forming coating liquid A>

[0595] Ionizing radiation curable compound 1: 0.6 parts by mass

[0596] (Compound α synthesized in "3")

[0597] Ionizing radiation curable compound 2: 0.2 parts by mass

[0598] (Dacel Corporation, trade name "EBECRYL 230", solid content 100%)

[0599] Ionizing radiation curable compound 3: 0.2 parts by mass

[0600] (Kyoeisha Chemical Co., Ltd., product name: "Light Acrylate IAA", solid content: 100%)

[0601] Leveling agent: 0.01 parts by mass

[0602] (Dainichi Seika Industries, trade name: "10-28 (TL)"), solid content: 10% by mass)

[0603] Photopolymerization initiator: 0.1 parts by mass

[0604] (IGM Resins BV, trade name "Omnirad 184"

[0605] Solvent

[0606] (A 5:5 mixed solvent of methyl isobutyl ketone and cyclohexanone. The solvent was used in such an amount that the solid content of the coating liquid became 35% by mass.)

[0607] <Hard coat layer forming coating liquid B>

[0608] · Ionizing radiation curable compound 1: 1 part by mass

[0609] (Compound α synthesized in "3")

[0610] Acrylic resin particles: 0.1 parts by mass

[0611] (Average particle size: 2 μm, refractive index: 1.535)

[0612] Leveling agent: 0.01 parts by mass

[0613] (Dainichi Seika Industries, trade name: "10-28 (TL)"), solid content: 10% by mass)

[0614] Photopolymerization initiator: 0.1 parts by mass

[0615] (IGM Resins BV, trade name "Omnirad 184"

[0616] Solvent

[0617] (A 5:5 mixed solvent of methyl isobutyl ketone and cyclohexanone. The solvent was used in such an amount that the solid content of the coating liquid became 35% by mass.)

[0618] <Hard coat layer forming coating liquid C>

[0619] Ionizing radiation curable compound 1: 0.625 parts by mass

[0620] (Compound α synthesized in "3")

[0621] Ionizing radiation curable compound 4: 0.375 parts by mass

[0622] (Arakawa Chemical Industries, trade name: OPSTARZ7415, solid content: 100%)

[0623] Leveling agent: 0.01 parts by mass

[0624] (Dainichi Seika Industries, trade name: "10-28 (TL)"), solid content: 10% by mass)

[0625] Photopolymerization initiator: 0.1 parts by mass

[0626] (IGM Resins BV, trade name "Omnirad 184"

[0627] Solvent

[0628] (A 5:5 mixed solvent of methyl isobutyl ketone and cyclohexanone. The solvent was used in such an amount that the solid content of the coating liquid became 35% by mass.)

[0629] <Coating liquid i for forming low refractive index layer>

[0630] Composition containing ultraviolet curable acrylate: 1 part by mass

[0631] (Nippon Kayaku Co., Ltd., trade name "KAYARAD PET-30", solid content: 100%)

[0632] Photopolymerization initiator: 0.1 parts by mass

[0633] (IGM Resins BV, trade name "Omnirad 127"

[0634] Hollow silica particles: 1.3 parts by mass

[0635] (Average primary particle size: 60nm)

[0636] Solid silica particles: 0.7 parts by mass

[0637] (Average primary particle size: 15nm)

[0638] Leveling agent: 0.1 parts by mass

[0639] (Shin-Etsu Chemical Co., Ltd., trade name "X-22-164E")

[0640] Solvent

[0641] (A 5:5 mixed solvent of methyl isobutyl ketone and cyclohexanone. The solvent was used in such an amount that the solid content of the coating liquid became 2% by mass.)

[0642] <Coating liquid for forming low refractive index layer ii>

[0643] Composition containing ultraviolet curable acrylate: 1 part by mass

[0644] (Nippon Kayaku Co., Ltd., trade name "KAYARAD PET-30", solid content: 100%)

[0645] Photopolymerization initiator: 0.1 parts by mass

[0646] (IGM Resins BV, trade name "Omnirad 127"

[0647] Hollow silica particles: 1.55 parts by mass

[0648] (Average primary particle size: 60nm)

[0649] Solid silica particles: 0.45 parts by mass

[0650] (Average primary particle size: 15nm)

[0651] Leveling agent: 0.1 parts by mass

[0652] (Shin-Etsu Chemical Co., Ltd., trade name "X-22-164E")

[0653] Solvent

[0654] (A 5:5 mixed solvent of methyl isobutyl ketone and cyclohexanone. The solvent was used in such an amount that the solid content of the coating liquid became 2% by mass.)

[0655] <Coating liquid for forming low refractive index layer iii>

[0656] Composition containing ultraviolet curable acrylate: 1 part by mass

[0657] (Nippon Kayaku Co., Ltd., trade name "KAYARAD PET-30", solid content 100%)

[0658] Photopolymerization initiator: 0.1 parts by mass

[0659] (IGM Resins BV, trade name "Omnirad 127"

[0660] Hollow silica particles: 2 parts by mass

[0661] (Average primary particle size: 60nm)

[0662] Leveling agent: 0.1 parts by mass

[0663] (Shin-Etsu Chemical Co., Ltd., trade name "X-22-164E")

[0664] Solvent

[0665] (A 5:5 mixed solvent of methyl isobutyl ketone and cyclohexanone. The solvent was used in such an amount that the solid content of the coating liquid became 2% by mass.)

[0666] 5. Production of optical films

[0667] [Experimental Example 1-1]

[0668] As the optical film of Experimental Example 1-1, the polyester film 3 prepared in “2” was prepared. The optical film of Experimental Example 1-1 did not have a hard coat layer and a low refractive index layer on the polyester film 3 .

[0669] [Experimental Example 1-2]

[0670] The hard coat layer-forming coating liquid A was applied to the polyester film 3 prepared in "2", and then dried at 70°C for 1 minute to volatilize the solvent. Then, ultraviolet irradiation (100 mJ / cm 2 ) to form a hard coating layer (dry thickness: 10 μm).

[0671] The coating liquid i for forming a low refractive index layer was applied onto the hard coat layer, and then dried at 60° C. for 1 minute to volatilize the solvent. Then, ultraviolet irradiation (200 mJ / cm2 ) to form a low refractive index layer (dry thickness is 100nm) to obtain the optical film of Experimental Example 1-2.

[0672] [Experimental Examples 1-3, 1-4]

[0673] Optical films of Experimental Examples 1-3 and 1-4 were obtained in the same manner as in Experimental Example 1-2, except that the coating liquids described in Table 1 were used as the coating liquid for forming a hard coat layer and the coating liquid for forming a low refractive index layer.

[0674] [Experimental Example 1-5]

[0675] An optical film of Experimental Example 1-5 was obtained in the same manner as in Experimental Example 1-2 except that the low refractive index layer was directly formed on the polyester film without forming a hard coat layer and that the coating liquid described in Table 1 was used as the coating liquid for forming the low refractive index layer.

[0676] [Experimental Example 2-1]

[0677] As the optical film of Experimental Example 2-1, the polyester film 2 produced in “2” was prepared. The optical film of Experimental Example 2-1 did not have a hard coat layer and a low refractive index layer on the polyester film 2 .

[0678] [Experimental Example 2-2]

[0679] An optical film of Experimental Example 2-2 was obtained in the same manner as in Experimental Example 1-2 except that the polyester film 3 was changed to the polyester film 2.

[0680] [Experimental Examples 2-3, 2-4]

[0681] Optical films of Experimental Examples 2-3 and 2-4 were obtained in the same manner as in Experimental Example 2-2 except that the coating liquids described in Table 1 were used as the coating liquid for forming a hard coat layer and the coating liquid for forming a low refractive index layer.

[0682] [Experimental Examples 2-5, 2-6]

[0683] Optical films of Experimental Examples 2-5 and 2-6 were obtained in the same manner as in Experimental Example 2-2, except that the low refractive index layer was directly formed on the polyester film without forming a hard coat layer and that the coating liquid described in Table 1 was used as the coating liquid for forming the low refractive index layer.

[0684] [Experimental Examples 3-1, 3-2]

[0685] Optical films of Experimental Examples 3-1 and 3-2 were obtained in the same manner as in Experimental Example 1-2 except that the polyester film 3 was changed to the polyester film 1 and the coating liquids described in Table 1 were used as the coating liquid for forming a hard coat layer and the coating liquid for forming a low refractive index layer.

[0686] [Experimental Example 3-3]

[0687] The optical film of Experimental Example 3-3 was obtained by changing the polyester film 3 to the polyester film 1, and changing the hard coating layer to be formed directly on the polyester film instead of forming the hard coating layer, and further using the coating liquid described in Table 1 as the coating liquid for forming the low refractive index layer.

[0688] [Table 1]

[0689]

[0690] [Table 2]

[0691] Table 2

[0692]

[0693] From the results in Table 1, we can confirm that: T The optical film with a value greater than 0.04 and less than 0.20 can eliminate rainbow spots when observed with the naked eye and improve the uniformity of color tone when observed from an oblique direction. In the experimental examples in Table 1, the examples corresponding to the embodiments are Experimental Examples 1-2, 1-3, 1-4, 2-2, 2-3, 2-4, 2-6, 3-1, and 3-2.

[0694] In addition, from the results in Tables 1 and 2, it can be confirmed that "a film having a small in-plane phase difference of the plastic film" and "a film having a large difference between the maximum value and the minimum value in the direction of the slow axis of the plastic film" are easy to make Σ T The value of is an appropriate value.

[0695] Furthermore, the results in Table 2 show that, regardless of the bending direction, the polyester films 1 and 2 can suppress the occurrence of creases or breaks after the bending test. The polyester films 1 and 2 are "films having large differences between the maximum and minimum values ​​in the slow axis direction of the plastic film".

[0696] In addition, no microcracks were observed after the bending test for the polyester films 1 and 2. Microcracks can be observed as follows.

[0697] Microcracks can be observed using a digital microscope. Examples of the digital microscope include a digital microscope with a trade name of "VHX-5000" manufactured by KEYENCE Corporation.

[0698] Regarding microcracks, annular illumination was selected as the illumination of the digital microscope, and observation was performed using a dark field and reflected light. Specifically, first, the sample after the bending test was slowly unfolded, and then the sample was fixed on the workbench of the microscope with tape. At this time, if the crease is strong, the area to be observed is made as flat as possible. When performing the above operation, be careful not to touch the bent portion of the sample as the evaluation object area with your hands, and do not apply force to the bent portion. Then, both the part that becomes the inside and the part that becomes the outside during the bending test are evaluated.

[0699] The observation of microcracks was carried out in a bright room with white lighting (illuminance of 1000 lux to 2000 lux).

[0700] Description of symbols

[0701] 10: Plastic film;

[0702] 20: Hard coating;

[0703] 30: low refractive index layer;

[0704] 100: optical film;

[0705] 200: surface light source;

[0706] 300: Polarizer;

[0707] 400: adhesive layer;

[0708] 500: 1st transparent protective plate;

[0709] 600: second transparent protective plate;

[0710] 700: Polarizing plate;

[0711] 800: display element;

[0712] 1000: image display device;

[0713] A1: light source;

[0714] A2: Detector;

[0715] S: slow axis;

[0716] F: fast axis;

[0717] V: vibration direction of light L1;

[0718] 11: container;

[0719] 12: Receiver;

[0720] 21: Piping for test fluid;

[0721] 22: Piping for compressed air;

[0722] 23: Return piping;

[0723] 24: Return pump;

[0724] 31, 32: flow meter;

[0725] 41, 42: pressure gauge;

[0726] 50: injection part;

[0727] 51: nozzle;

[0728] 52: housing;

[0729] 60: cross-sectional profile obtaining unit;

[0730] 70: plastic film;

[0731] 81: Sample mounting table;

[0732] 82: support body;

[0733] 90: Erosion rate measuring device;

[0734] A1: water;

[0735] A2: spherical silica;

[0736] A3: Air;

[0737] A4: The plastic film is worn out.

Claims

1. An optical film having a low refractive index layer on a plastic film, wherein: The plastic film has: a slow axis, which is an axis with the largest refractive index in a plane; and a fast axis, which is an axis orthogonal to the slow axis in the plane of the plastic film. The low refractive index layer is located on the surface of the optical film. The optical film has a Σ that satisfies the following measurement condition 1 T In the area exceeding 0.04 and less than 0.20, <Measurement condition 1> A linearly polarized light is incident from the surface of the optical film opposite to the low refractive index layer, the linearly polarized light as the incident light is defined as light L1, and the transmitted light after the light L1 passes through the optical film is defined as light L2; The light L1 is made incident on the optical film at the following angle, wherein the angle is such that the elevation angle of the vibration direction of the light L1 is greater than 50 degrees and less than 70 degrees based on the plane of the optical film, while the angle formed by the slow axis and the vibration direction of the light L1 is fixed at 45 degrees, and the elevation angle is changed by 2 degrees within the range of greater than 50 degrees and less than 70 degrees, and the light L2 is measured at 11 elevation angles, and the light L2 is measured at 11 measurement points through the above-mentioned measurement; The light L2 is converted into the conditions of C light source and a viewing angle of 2 degrees, and the a* value and b* value of the L*a*b* colorimetric system are defined as a*n and b*n for the light L2 at the nth measurement point among the 11 measurement points, and the a* value and b* value of the L*a*b* colorimetric system are defined as a*n1 and b*n1 for the light L2 at the n+1th measurement point among the 11 measurement points; Based on the measurements of the 11 measurement points, the sum of the square of the difference between the a* of the adjacent measurement points and the square of the difference between the b* of the adjacent measurement points is calculated, the sum is calculated at each of the 10 adjacent points, and ∑ T , the Σ T It can be expressed by the following formula 1: ∑ T = ∑[{a*n - a*n1} 2 + {b*n - b*n1} 2 (Equation 1).

Citation Information

Patent Citations

  • Polarizing plate protection film, polarizing plate and liquid crystal display apparatus using same

    JP2009014886A

  • Polarizing plate protection film, polarizing plate and liquid crystal display apparatus

    JP2010204630A

  • Visibility improving method of liquid crystal display device, and liquid crystal display device using the same

    JP2011107198A

Cited By

  • Optical film, polarizing plate, image display device, and method for selecting optical film

    CN116529638A

  • Optical film, polarizing plate, image display device, and method for selecting optical film

    CN116529638B